Layered and zoned catalyst articles
By adopting a layered and partitioned structure in the catalyst, combining platinum group metals and porous support materials, the problems of existing catalysts being inactivated under high temperature conditions and difficult to effectively remove emissions are solved, and higher catalytic activity and durability are achieved.
Patent Information
- Application Number
- CN202380043413.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-30
- Filing Date
- 2023-03-30
- Publication Date
- 2025-03-14
AI Technical Summary
Existing catalysts are inactivated under high temperature conditions and it is difficult to effectively remove CO, HC, hydrogen and NOX from diesel engine emissions, especially under lean combustion conditions.
Catalyst products employing layered and partitioned structures, containing platinum group metal elements such as platinum and palladium, combined with porous support materials such as alumina and silicon oxide, and introduced porous metal oxides and promoters into the catalyst to improve catalytic activity and durability.
It improves the stability and activity of the catalyst under high temperature conditions, enhances the oxidation capacity of CO, HC, hydrogen and NOX, and effectively reduces the concentration of emissions.
Smart Images

Figure CN119630468A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to layered and zoned catalyst articles (1), which in preferred embodiments comprise platinum group metal (PGM) elements, such as platinum (Pt) and palladium (Pd), and porous support materials, such as aluminum oxide (Al2O3), silicon oxide (SiO2), titanium oxide (TiO2), and optionally other metal oxides and promoters, which can be used to produce catalysts for the oxidation of carbon monoxide (CO), hydrocarbons (HC), hydrogen (H2) and nitrogen oxides (NO X ) emissions, the layered catalyst product (1) is also suitable for use as a temporary NO X and hydrocarbon storage for total NOx reduction X and hydrocarbon emissions. The present disclosure describes the composition of a catalyst article (1) and how to use such a catalyst article (1) in purifying exhaust emissions. Background Art
[0002] When a diesel engine is operated under lean conditions (λ>1), the exhaust gas emitted by the lean burn engine will contain residual amounts of hydrocarbons (HC) and carbon monoxide (CO). In order to control the harmful emissions, these compounds are often oxidized in a diesel oxidation catalyst (DOC) into less harmful exhaust compounds, such as carbon dioxide (CO2) and water (H2O). And, in addition to these exhaust compounds, lean burn engines emit nitrogen oxides (NO X ) and particulate matter (PM).
[0003] Due to the demand for lower carbon dioxide (CO2) emissions (ie, lower fuel consumption and temperatures) in both light-duty and heavy-duty lean applications, as well as increasingly stringent emission limits set by governmental authorities on pollutants, there is a continuing need in the art for improved catalyst systems.
[0004] Although NO X and particulate matter (PM) are usually removed by exhaust gas aftertreatment units, such as NO X The SCR and PM are removed by urea, while the SCR and PM are oxidized by the DPF. NO2 can also be formed by the oxidation of NO on the DOC.
[0005] It is known in the art that lean NO X Traps (LNT) are applied to exhaust gases, which are lean on average, to store NO during long lean periods X, and periodically reduce the exhaust gas during short rich (λ<1) periods, such as 2-5 seconds. Due to fuel economy and the need for no additional reducing agent in order to obtain a compact system, lean NO X Trapping (LNT) is more popular in light-duty diesel and gasoline applications than in heavy-duty diesel applications.
[0006] In this field, lean NO X A combination of a trap (LNT) and a selective catalytic reduction (SCR) unit, where, for example, in the case of lean NO X The excess ammonia (NH3) formed during the rich phase of the trap (LNT) is used to lean NO X in a selective catalytic reduction (SCR) unit downstream of the capture (LNT).
[0007] In removing the total NO X Passive NO emissions X The adsorbent (PNA) can temporarily store NO upstream of the selective catalytic reduction (SCR) catalyst. X The stored NO is then released at a temperature favorable for the selective catalytic reduction (SCR) reaction, for example, above 200°C. X Compound.
[0008] Since the temperature of diesel exhaust gas is usually in the range of 100-500°C, depending on the driving state, high CO and hydrocarbon (HC) oxidation activity of the catalyst is required to avoid cold start emissions caused by insufficient catalyst warm-up.
[0009] Typically, the carbon present in the particulate matter (PM) is already regenerated in the diesel particulate filter (DPF) either continuously passively at low temperatures (<230°C) with NO2 (C+NO2, slow reaction) or actively (C+O2, fast reaction) by periodic fuel (hydrocarbon) injection and throttling to raise the temperature to the carbon oxidation temperature (about 600°C). Depending on the active diesel particulate filter (DPF) regeneration strategy selected, high hydrocarbon concentrations in the exhaust gas (e.g. 0.5-2.0 vol%) increase the hydrocarbon light-off temperature (T) on the DOC. 50 ).
[0010] It is well known that high hydrocarbon concentrations inhibit the oxidation of CO, hydrocarbons and NO, and therefore the hydrocarbon light-off temperature is significantly increased by up to 50-100°C compared to normal diesel exhaust conditions (@<500ppm hydrocarbons). Accordingly, high NO to NO2 oxidation activity at low temperatures (<230°C) is required to achieve high performance of the selective catalytic reduction (SCR). High CO, hydrocarbon and NO oxidation activities are required to meet current emission limits and predetermined engineering targets.
[0011] At present, when diesel engines are running at close to maximum power, exhaust gas temperatures are usually above 400-500°C. Especially when the active catalyst is regenerated, the exhaust gas temperature is high. Even under controlled diesel particulate filter (DPF) regeneration conditions, the temperature should not usually exceed 650°C, and the diesel oxidation catalyst (DOC) is still designed to withstand some uncontrolled particulate matter (PM) oxidation or diesel particulate filter (DPF) regeneration with peak temperatures up to 700-800°C without increasing activity loss. However, at the highest temperatures, the catalyst must maintain good long-term stability to maintain high catalytic activity throughout the life of the catalyst.
[0012] It is well known in the art that platinum (Pt) has good CO, hydrocarbon and NO oxidation activity. However, the thermal durability of platinum is considered mediocre compared to other alternatives known in the art. In order to increase the thermal durability of Pt, palladium (Pd) is usually added to diesel exhaust catalysts. Pd is also a commonly used component in diesel oxidation catalysts (DOCs) because it has good activity and selectivity for the oxidation of hydrocarbons and CO.
[0013] The catalytic performance of Pt and Pd is different for different types of hydrocarbons, and for exhaust gases containing saturated / unsaturated and light / heavy hydrocarbons (also oxygenated hydrocarbons), a combination of Pt and Pd is generally considered necessary. However, the Pd pair is very susceptible to deactivation in the presence of sulfur. Due to the high price of platinum group metals (PGM), especially Pd, alternative materials for improving catalyst stability are needed.
[0014] The observation that Pt and Pd have different properties and activities in catalytic reactions under dilute conditions has long produced the idea of having partitioned catalytic materials in catalysts for internal combustion engines (US3947545, Toyota). Similarly, layered catalysts are also well known in the art, with reference to, for example, GB1330842A, which describes in detail a catalyst comprising a bottom metal oxide and a top platinum group metal and metal oxide.
[0015] It is well known that sulfur compounds such as sulfur oxides (SO X) can affect the performance of the aftertreatment system. In current aftertreatment systems, a diesel oxidation catalyst (DOC) is usually used as the first catalyst unit in the flow direction. Sulfur-containing compounds can react with the catalyst surface of the diesel oxidation catalyst (DOC), making the catalyst less effective in removing harmful exhaust components (such as CO, hydrocarbons and NOx). X ) is less efficient. In addition, sulfur-containing particles may be trapped on the diesel particulate filter. However, usually under high temperature conditions, such as above 500°C, such accumulated sulfur compounds will be released from the catalyst.
[0016] Diesel exhaust may contain other impurities such as phosphorus, zinc or silicon from, for example, lubricants, oils and / or fuels. Furthermore, these impurities can reduce the performance of the catalytic system and their presence in the aftertreatment system unit should be avoided. In contrast to sulfur, catalyst poisoning by other chemical elements and compounds is generally irreversible, with the result that the activity of the catalyst cannot be restored.
[0017] In addition to the effects of impurities present in the exhaust gas stream, catalyst activity can also be reduced due to exposure of the catalytic system to higher exhaust gas temperature conditions (e.g., above 800° C.). The negative effects of high temperature conditions (e.g., in the presence of water) can be partially avoided by utilizing appropriately selected materials known in the art, and by improving the preparation methods for catalyst manufacturing. In addition, minimizing the exposure time to high temperature conditions can reduce catalyst deactivation.
[0018] In the art, alumina (e.g., Al2O3), silica (e.g., SiO2) and / or mixtures thereof are well known as porous support materials for catalysts used in lean burn operation applications. For example, alumina is a well known porous support material for providing a high surface area for platinum group metal (PGM) components. When silica and alumina are used together, they improve the thermal and chemical stability of the catalyst.
[0019] The purpose of the porous support material in the catalyst articles of the prior art and the catalyst articles (1) of the present disclosure is to provide a solid matrix for carrying various reaction promoters and to provide a high surface to allow the desired contact of gas molecules for various catalytic improvement reactions desired in the art. In the art and herein, such a solid matrix for carrying reaction promoters is referred to as a support, and the material capable of forming a support is referred to as a support material. The same applies to the terms used herein.
[0020] In the art, for example, Si- (e.g. EP 0377290), Ti- (e.g. JP 4087627), Si-Ti- (e.g. US 5,145,825) and / or Zr-oxide supports are known to provide catalysts that adsorb less sulfate and have been applied to catalysts to improve sulfur resistance in diesel oxidation catalysts (DOCs). The effects of various reaction promoter substitutes, such as Sc, Ti, Cr, Mn, Fe, Co, Cu, La, Au, Ag, Ga, In, Ce, V, Mo, W, Zr, Nb, Pr, and zeolites of different effects have also been proposed in the prior art (see, for example, WO2004091782).
[0021] Different reaction promoters can be adjusted according to the PGM composition or particle size. The PGM composition can be adjusted for example for zeolite or ceria. When aluminum (Al) and cerium (Ce) oxides are used for SO X When adsorbed, it has been shown that it is possible to decompose sulfur-containing substances at moderate temperatures. When using components such as lanthanum (La), barium (Ba) and yttrium (Y), more stable sulfates are produced by catalysis, see for example WO1993022050A1. Similarly, zeolites have been applied to Pt-DOCs together with aluminum and cerium oxides since the 1990s, see for example WO9401926. In the art, tungsten (W) has also been used in emission catalysts for selective catalytic reduction (SCR) (VW / TiO2) and TWC, see for example EP0056729.
[0022] Furthermore, in the DOC field, many different types of reaction promoters and PGM loadings / ratios have been proposed, especially as single compositions. However, many additives are reaction promoters for certain properties, but have no effect or even a negative effect on other properties. For example, the best composition for hydrocarbon light-off may be quite poor in NO oxidation, and similarly, the best catalyst for NO oxidation may have limitations in hydrocarbon and CO oxidation. Furthermore, local PGM distribution / dispersion and mass / heat transfer play an important role in the catalyst reaction chain and durability.
[0023] Considering the above-mentioned complexity of catalyst design and due to strict emission regulations, it is necessary to develop oxidation and lean catalysts and aftertreatment systems (ATS) with improved performance and high cost efficiency. To achieve this goal, the use of PGM components and related support material components has become increasingly important to ensure good performance and long-term durability.
[0024] The catalyst article (1) of the present disclosure performs the catalytic reactions involved in a catalytic aftertreatment system (ATS) to purify and oxidize exhaust emissions from engine lean operating conditions. The catalyst article (1) of the present disclosure is used to oxidize and remove carbon monoxide (CO), hydrocarbons (HC), hydrogen (H2) and nitrogen monoxide (NO) to nitrogen dioxide (NO2), as well as to increase nitrogen oxides (NO X ) removal efficiency.
[0025] The catalyst product (1) of the present disclosure may also include NO X Adsorption performance to NO X The emissions are temporarily stored at a designated location on the catalyst article (1) so that the total NO X Emissions are reduced. These catalytic functions achieved through multiple layers and zones according to the present disclosure can be applied in the same catalyst article (1).
[0026] Definitions and Abbreviations
[0027] λLambda, air-fuel equivalence ratio
[0028] γ(Gamma)
[0029] ASC—Ammonia Slip Catalyst
[0030] ATS—Aftertreatment System
[0031] BET—Brunauer-Emmett-Teller, specific surface area calculation method
[0032] CeO X —Cerium oxide
[0033] cpsi—cells per square inch
[0034] deNO X —Removal of nitrogen oxides
[0035] DOC - Diesel Oxidation Catalyst
[0036] DPF - Diesel Particulate Filter
[0037] Total Available Active Metals per Volume: PGM, component or coating loading in g / L units, grams of PGM, component or coating per volume of total substrate, volume units are liters. The volume loading of PGM is meaningful for understanding the total PGM added (total available active metal per volume) without knowing the exact geometric area of the substrate, coating density.
[0038] HC—Hydrocarbon
[0039] HT—Hydrothermal
[0040] HT700—700℃ hydrothermal (aging)
[0041] In-B—Inlet bottom, inlet near end
[0042] In-T—Inlet top layer, inlet far end
[0043] LaO X —Lanthanum oxide
[0044] LNT—Lean burn NO X Capture
[0045] NO X —Nitrogen oxides
[0046] Out-B—Outlet bottom, outlet near end
[0047] Out-T—Outlet top layer, outlet far end
[0048] PNA—Passive NO X Adsorbent
[0049] PGM—Platinum Group Metals
[0050] SAR—Si / Al2 ratio, molar
[0051] SCR - Selective Catalytic Reduction
[0052] SGB—Syngas Bench
[0053] SO X — Sulfur oxides
[0054] SV—Airspeed
[0055] T 50 Ignition temperature, the temperature at which 50% conversion is achieved
[0056] TWC—Three-Way Catalyst
[0057] WHTC—World Uniform Transient Cycle
[0058] WO X —Tungsten oxide
[0059] ZrO X —Zirconium oxide Summary of the invention BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figures 1 to 7 are illustrations of exemplary embodiments of catalyst articles (1) of the present disclosure and of the prior art. Figures 8 to 17 Experimental records illustrating the technical benefits of the present disclosure.
[0061] Figure 1 A catalyst article (1) of the present disclosure is shown, which includes an inlet bottom (In-B) coating, an outlet bottom (Out-B) coating, an inlet top (In-T) coating, and an outlet top (Out-T) coating, which are adjacent to each other and stacked.
[0062] Figure TRB shows a catalyst article (1) of the present disclosure, which includes an inlet bottom layer (In-B) coating, an outlet bottom layer (Out-B) coating, an inlet top layer (In-T) coating, and an outlet top layer (Out-T) coating, which are adjacent to each other and stacked, and the coating length and thickness are variable. As shown in detail, the overlapping top and bottom layers form a Figure 5 Consistent middle partition. In the embodiment of Figure TRB, In-T overlaps with Out-B, forming a middle partition, but the reverse is equally possible, Out-T overlaps with In-B, but this is not shown here.
[0063] FIG3 shows a catalyst article (1) of the prior art, which includes an inlet bottom layer (In-B) coating, an outlet bottom layer (Out-B) coating identical to the In-B coating, an inlet top layer (In-T) coating and an outlet top layer (Out-T) coating, which are adjacent to each other and stacked. In the art, such a catalyst article (1) is manufactured by first coating the bottom layer (according to the attached figure, coating In-B and Out-B at the same time), and then adding two different top layers In-T and Out-T. In the present disclosure, the samples prepared with the coating structure according to FIG3 are prepared according to the methods described in Examples 12 and 13. Fig.17 The teachings of the present disclosure described in detail in the accompanying drawings use exemplary teachings.
[0064] Figure 2 A catalyst article (1) of the prior art is shown, which includes an inlet bottom layer (In-B) coating, an outlet bottom layer (Out-B) coating identical to the In-B coating, an inlet top layer (In-T) coating, and an outlet top layer (Out-T) coating identical to the In-T coating, which are stacked.
[0065] The present disclosure relates to a catalyst article (1) carrying at least two partitions, characterized in that the at least two partitions contain at least two chemically different layers (In-B, In-T or Out-B, Out-T), and at least the inlet bottom layer is chemically or morphologically different from the outlet bottom layer, and the inlet bottom layer is chemically or morphologically different from the outlet bottom layer.
[0066] Figure 5The catalyst article (1) of the present invention is shown, which includes three partitions, an inlet partition, a middle partition and an outlet partition, formed by an inlet bottom layer (In-B) coating, a middle bottom layer (Mid-B) coating, an outlet bottom layer (Out-B) coating, an inlet top layer (In-T) coating, a middle top layer (Mid-T) coating and an outlet top layer (Out-T) coating, which are adjacent to each other and stacked.
[0067] Figure 6 The catalyst article (1) of the present invention is shown, which includes three partitions, an inlet partition, a middle partition and an outlet partition, formed by an inlet bottom layer (In-B) coating, an outlet bottom layer (Out-B) coating, a middle (Mid) coating, an inlet top layer (In-T) coating and an outlet top layer (Out-T) coating, which are adjacent to each other and stacked.
[0068] Figure 7 A catalyst article (1) of the present disclosure is shown, which includes an inlet bottom layer (In-B) coating, an outlet bottom layer (Out-B) coating, an inlet top layer (In-T) coating, an outlet top layer (Out-T) coating and a second top layer (second top layer) coating, which are adjacent to each other and stacked.
[0069] Figure 8 The differences in NO oxidation to NO2 (%) measured after a diesel engine steady-state test between a layered catalyst article (1) comprising W+Pt (Example 1), a single-layer coating composition comprising W+Pt (Example 2) and a single-layer REF (Example 3) are shown.
[0070] Fig. 9 The difference in NO oxidation to NO2 (%) measured in the SGB test for a zoned / layered sample containing Pt+Pd+W (Example 4) and a layered sample containing Pt+W (Example 5) and a layered sample containing Pt+Pd (Example 6) after HT700 aging is shown.
[0071] Fig.10 The CO and THC ignition temperatures (°C, T) measured in the SGB test for zoned / layered samples containing Pt+Pd+W (Example 4), layered samples containing Pt+W (Example 5), and layered samples containing Pt+Pd (Example 6) after HT700 aging under normal and regeneration conditions are shown. 50 ) differences.
[0072] Fig.11The difference in NO oxidation to NO2 (%) measured in the SGB test for a zoned / layered sample containing Pt+Pd+W (Example 7) and a zoned / layered sample containing Pt+Pd (Example 8) after HT700 aging is shown.
[0073] Fig.12 The difference in NO oxidation to NO2 (%) measured in the SGB test for a zoned / layered sample containing Pt+Pd+W (Example 7) and a zoned / layered sample containing Pt+Pd (Example 8) after HT700+SO2 aging is shown.
[0074] Fig.13 The THC ignition temperature (°C, T) measured in the SGB test for the zoned / layered sample containing Pt+Pd+W (Example 7) and the zoned / layered sample containing Pt+Pd (Example 8) after HT700+SO2 aging is shown. 50 ) differences.
[0075] Fig.14 The difference in NO oxidation to NO2 (%) measured in the SGB test for a zoned / layered sample containing Pt+Pd+W (Example 9) and a zoned / layered sample containing Pt+Pd (Example 10) after HT700 aging is shown.
[0076] Fig.15 The CO and THC ignition temperatures (°C, T) measured in the SGB test for the zoned / layered sample containing Pt+Pd+W (Example 9) and the zoned / layered sample containing Pt+Pd (Example 10) after HT700 aging are shown. 50 ) differences.
[0077] Fig.16 The relative desorption of NO from freshly layered samples (Examples 11a-g) is shown. X (%) as a function of temperature.
[0078] Fig.17 The difference in NO oxidation to NO2 (%) measured in the SGB test is shown for the zoned catalyst preparation (1).
[0079] It should be understood that the embodiments shown in the accompanying drawings are for the purpose of illustrating the present invention and cannot be interpreted as limiting the present invention. Unless otherwise specified, the accompanying drawings are intended to be read together with the specification (e.g., section lines, component arrangement, proportions, degrees, etc.) and are considered to be part of the entire written description of the present disclosure. DETAILED DESCRIPTION
[0080] As described in detail herein above, layered catalyst articles are commonly used in the art. In such layered catalyst articles, two layers of different chemical nature are typically used in order to promote one or more conversion reactions over the length of the catalyst article.
[0081] In a layered catalyst article, one layer will be in contact with the surface of the underlying substrate (2) and form a proximal coating on the underlying substrate, with more distal layers successively forming on top of the corresponding underlying coating and thus closer to the underlying substrate. This principle is observed in the direction of gas flow through the catalyst article. Figure 2 and shown in Figure 3, and in Figure 1 Partially shown in C.
[0082] In order to maintain gas flow through the catalyst article (1), there is a limit to how much gas passages can be reduced across the catalyst article by adding additional catalytic coatings before the pressure drop across the catalyst article becomes a limiting factor for proper operation of the tool in which the catalyst article is installed.
[0083] At the same time, the possible volume of the engine assembly that can be allocated to the catalyst article for exhaust gas conversion is limited by the design constraints of the engine assembly, so that the catalytic performance cannot be improved simply by changing the size of the catalyst article known in the prior art.
[0084] Therefore, it is crucial to optimize the catalytic conversion on the catalyst preparation.
[0085] The present disclosure relates in a first aspect and embodiment to a layered (or zoned) and partitioned catalyst article (1), wherein by appropriately selecting the catalytically active components in the catalytic layer, a catalyst article (1) having at least two catalytic partitions (10, 20, 30) is produced, each catalytic partition selectively catalytically converting one or more chemical exhaust components contained in the exhaust gas from a fuel combustion or explosion engine into one or more desired release components.
[0086] Surprisingly, the inventors have discovered that by selectively dividing a catalyst article for exhaust gas conversion into smaller catalytically active partitions, wherein a given partition is catalytically active for different exhaust gas components compared to the remaining catalytically active partitions, an overall improvement in exhaust gas conversion can be achieved at the expense of only a slight decrease, if any, in exhaust gas quality for individual undesirable gas components in the exhaust gas.
[0087] In the present disclosure, the principles of the present invention are discussed based on a catalyst article (1) comprising two catalytic partitions (10, 20), wherein the first catalytic partition (10) selectively converts hydrocarbons (HC), H2 or carbon monoxide (CO) in the exhaust gas into water and carbon dioxide, and the second catalytic partition (20) selectively converts nitrogen monoxide into nitrogen dioxide, and / or converts sulfur monoxide into sulfur dioxide.
[0088] By selectively removing hydrocarbons, hydrogen and / or carbon monoxide to below the critical level of second zone pollution, NO X / SO X The operation of the oxidation catalyst can be maintained efficiently, thereby optimizing the total catalyst volume on the catalyst article of the present invention.
[0089] Therefore, in a first aspect and in an embodiment, a catalyst product (1) for exhaust gas purification under lean exhaust gas conditions is described in detail herein, comprising a channel (3), the channel (3) being used to allow exhaust gas to pass through the catalyst product (1), thereby defining an inlet and an outlet of the channel for exhaust gas, and a flow direction of exhaust gas passing through the channel of the catalyst product (1), the channel (3) having a substrate (2) surface for carrying one or more catalytically active layers (11, 12, 21, 22), the catalytically active layers (11, 12, 21, 22) being used to convert at least a corresponding first and a corresponding second undesirable chemical component contained in the exhaust gas into at least a corresponding first or a corresponding second desired chemical component during the exhaust gas passing through the catalyst product (1);
[0090] - wherein at least a first and a second catalytic sub-area (10, 20) are arranged on the substrate (2), each respective catalytic sub-area (10, 20) comprising at least a respective first and a respective second catalytic layer (11, 12), (21, 22), arranged such that the first respective catalytic layer (11, 21) is close to the substrate (2) and the second respective catalytic layer (12, 22) is far from the substrate (2);
[0091] - wherein the first and second catalytic layers (11, 12, 21, 22) are each chemically different in pairs;
[0092] - wherein the first catalytic partition (10) is arranged in the channel (3) so that the exhaust gas passing through the channel (3) first encounters the first catalytic partition (10) before encountering the second catalytic partition (20); and
[0093] - wherein the second catalytic subzone (20) promotes the catalytic conversion of one of the corresponding first or second undesirable chemical components into the corresponding first or second desired chemical component, while the first catalytic subzone (10) does not substantially promote.
[0094] Figure 1 The general structure of the catalyst article (1) according to the present invention is shown in detail in FIG. The catalyst article (1) of the present disclosure has a substrate (2) surface, wherein at the inlet and outlet defined by the flow direction, two partitions (10, 20) start at the inlet (first partition) and end at the outlet (second partition), respectively, to produce the desired coating composition, present on the surface of the substrate (2). Although the partitions can start and end at positions different from the inlet and outlet, in practice they never do so for the spatial optimization of the catalyst article (1).
[0095] To simplify this document, the first proximal coating (11) is labeled and discussed as In-B, the first distal coating (12) is labeled and discussed as In-T, the second proximal coating (21) is labeled and discussed as Out-B, and the second distal coating (22) is labeled and discussed as Out-T. Thus, the inlet and outlet distal (top) coatings adhere to the inlet and outlet proximal (bottom) coatings. Thus, the bottom and top coatings described herein are defined relative to the surface of the substrate (2) rather than by weight, with the bottom layer being closest to the surface of the substrate (2) and the top layer being farthest from the surface of the substrate (2).
[0096] The substrate (2) is generally formed into a honeycomb structure and flow channels to maintain low pressure drop and has a high geometric surface for thin catalytic coatings. The surface of the substrate (2) is located on the walls and pores of the substrate (2) to form its internal flow channels, i.e., passages (3) in the language of the claims.
[0097] As discussed above and as Figure 2 As shown in Figure 3, it is known in the art to make layered catalyst articles. Figure 2 The catalyst article shown is a conventional two-layer catalyst article in which the top and bottom coatings are identical over the entire length of the catalyst article, so there is no layered catalyst.
[0098] In contrast, the catalyst article of FIG. 3 has a first and a second catalytic zone because the two top catalytic layers are chemically different. However, in the prior art, the bottom layer (in the language of the claims, the proximal layer) remains consistent. Typically, this structure does not allow the catalyst article to perform more than one catalytic action over the entire catalyst article, but allows for improved catalytic conversion by, for example, increasing the content of a catalyst promoter, such as expensive platinum or palladium in the second top layer disposed toward the outlet of the catalyst article, which can be kept low in the first zone because the content of the catalytic reactants is higher at the inlet of the exhaust gas into the catalyst article.
[0099] The present catalyst article (1) no longer utilizes this principle by making all four catalytic layers chemically different from each other. Therefore, it is possible to achieve true catalytic partitioning into at least two different catalytic partitions, so that the first catalytic partition (10) can promote a first catalytic conversion, while the second catalytic partition (20) can promote a different catalytic conversion that is not substantially promoted by the first catalytic partition (10).
[0100] In the context of the present application, a catalytic partition is considered to not substantially promote a catalytic reaction if a content of not more than 20%, preferably a content of not more than 15%, or preferably a content of not more than 10% of a particular chemical component is converted as a side reaction in a catalytic partition, which is otherwise configured to convert a different chemical component.
[0101] In a preferred embodiment of the present invention, the first catalytic partition (10) is configured to convert hydrocarbons, H2 and CO into water and CO2, and the second catalytic partition (20) is configured to convert NO X and / or SO X Converted to NO2 and / or SO3, NO X and / or SO X The conversion into NO2 and / or SO3 occurs in the second catalytic partition (20), essentially only in the second catalytic partition (20), while affecting the conversion rate in the first catalytic partition (10) (see experiments). Thus, the partition produced successfully achieves the separation of the two catalytic processes.
[0102] In a preferred embodiment, the first catalytic zone (10) achieves sufficient conversion of HC, H2 and CO to allow NO in the second catalytic zone (20). X / SO XThe conversion can occur without catalytic poisoning. However, as shown in the experiments, the second catalytic partition (20) thus formulated also successfully performs a secondary conversion of at least some of the unreacted HC, H2 and CO remaining in the exhaust gas, which is beneficial. Therefore, in the present invention, there is no strong restriction on the catalytic effect of the second catalytic partition (20) relative to the first catalytic partition (10), but there is a strong restriction relative to the first catalytic partition (10) in order to ensure that the second catalytic partition (20) can be used with maximum efficiency.
[0103] Also shown in the figure are various lengths indicating the length of the catalyst article (1) and the thickness of the various catalytic layers (11, 12, 21, 22). As described in detail herein below, in some embodiments, the variation of the layer dimensions (actually the layer volumes) forms part of the modification of the catalytic layers to obtain the full effect of the catalytic zoning of the present invention.
[0104] In some embodiments of the catalyst product (1) according to the present disclosure, in the flow direction of the exhaust gas through the channel (3), at least a third partition (30) is arranged in the channel (3) after the first catalytic partition (10) and before the second catalytic partition (20), such as Figures 4 to 6 Detailed display in.
[0105] exist Figure 4 An embodiment is shown in detail in which a third partition (30) is created by overlapping a first distal catalytic layer (12) with a second proximal catalytic layer (21), i.e., the In-T layer and the Out-B layer. The effect of this overlap is generally to avoid diffusion shortcuts caused by incompletely connected coatings, and in a preferred embodiment of the invention, the overlap also allows reactants to be stored in the second proximal catalytic layer (21) for improved catalytic conversion in the second catalytic partition (20) while also not terminating the HC, H2 and / or CO conversion occurring in the first distal catalytic layer (12).
[0106] Figure 4 The embodiment shown in detail in is particularly preferred in terms of ease of manufacture and use for catalytic conversions, as discussed above, however, it is clear that, if relevant, the third partition (30) can also be produced by overlapping the second distal catalytic layer (22) with the first proximal catalytic layer (11).
[0107] exist Figure 5 and Figure 6 A further embodiment of the third subzone (30) is shown in FIG. 1 , which may be useful in certain circumstances in the catalyst article (1) of the present invention.
[0108] exist Figure 5An embodiment is shown in detail in which the third partition (30) is intended to be a third catalytic partition (30), which has a third proximal catalytic layer and a third distal catalytic layer, and the third proximal catalytic layer and the third distal catalytic layer have chemical properties and reaction volumes suitable for performing a third catalytic conversion, and the third catalytic conversion is not performed by the first catalytic partition (10) or the second catalytic partition (20).
[0109] exist Figure 6 An embodiment is shown in detail in which the third partition (30) is a single layer connecting the aforementioned first and second catalytic partitions (10, 20). In some embodiments, for example, for manufacturing purposes, it may be beneficial to have a neutral region between the two catalytic partitions, which is reflected in the embodiment shown.
[0110] As described in detail above, in the most preferred embodiment of the present catalyst product (1), the first catalytic partition (10) selectively converts hydrocarbons, H2 and / or carbon monoxide (CO) in the exhaust gas into water and carbon dioxide, and the second catalytic partition (20) selectively converts nitrogen monoxide into nitrogen dioxide, and / or converts sulfur dioxide into sulfur trioxide.
[0111] According to the most preferred embodiment, in one embodiment, the first catalytic partition (10) contains one or more catalytically active metals selected from the platinum group metals (PGM) including Pt, Pd, Rh, Ir, Ru, and Os at a loading of less than 0.8 g / L in the first proximal catalytic layer (11); and contains one or more catalytically active metals selected from the platinum group metals (PGM) including Pt, Pd, Rh, Ir, Ru, and Os at a loading of 0.5-7.0 g / L in the first distal catalytic layer (12), provided that the metal loading in the first distal catalytic layer (12) should be higher than the metal loading in the first proximal catalytic layer (11).
[0112] According to the most preferred embodiment, in one embodiment, the platinum group metal selected for the first proximal catalytic layer (11) and the first distal catalytic layer (12) is platinum and / or palladium.
[0113] According to the most preferred embodiment, in one embodiment, platinum and palladium are present in the first distal catalytic layer (12) in a Pt:Pd ratio ranging from 1:4 to 5:1, and in the first proximal catalytic layer (11) in a Pt:Pd ratio ranging from 1:9 to 9:1.
[0114] According to the most preferred embodiment, in one embodiment, the second catalytic partition (20) comprises one or more catalytically active metals selected from the platinum group metals (PGM) including Pt, Pd, Rh, Ir, Ru, Os at a loading of less than 0.8 g / L in the second proximal catalytic layer (21); and comprises one or more catalytically active metals selected from the platinum group metals (PGM) including Pt, Pd, Rh, Ir, Ru, Os at a loading of 0.1-2.0 g / L in the second distal catalytic layer (22), provided that the metal loading in the second distal catalytic layer (22) should be higher than the metal loading in the second proximal catalytic layer (21), wherein the second distal catalytic layer (22) further comprises a catalyst sufficient to promote NO X The amount of tungsten (W) and / or molybdenum (Mo) converted into nitrogen dioxide.
[0115] According to the most preferred embodiment, in one embodiment, the platinum group metal selected for the second proximal catalytic layer (21) and the second distal catalytic layer (22) is platinum and / or palladium.
[0116] According to the most preferred embodiment, in one embodiment, the Pt:Pd ratio in the second distal catalytic layer (22) is 1:0 to 30:1, and the Pt:Pd ratio in the second proximal catalytic layer (21) is 1:9 to 9:1.
[0117] According to the most preferred embodiment, in one embodiment, the tungsten (W) in the second remote catalytic layer (22) is present in the form of tungsten oxide (WO3) in the range of 1 to 30 g / L.
[0118] According to the most preferred embodiment, in one embodiment, the PGM loading in the catalytic coating is in the order: In-T≥Out-T>In-B>Out-B, but preferably In-T>Out-T>In-B>Out-B.
[0119] According to the most preferred embodiment, in one embodiment, the first proximal catalytic layer (11) and the second proximal catalytic layer (21) further comprise cerium (Ce) oxide or cerium mixed oxide selected from ZrCe, MnCe, TiCe, PrCe oxide or a combination thereof, in an amount sufficient to promote NO X Adsorption-desorption and formation of NO2 by desorption at temperatures below 200°C.
[0120] According to the most preferred embodiment, in one embodiment, the cerium in the form of cerium oxide or cerium mixed oxide is present in an amount of 0.05 g / L to 0.5 g / L based on the total weight of the cerium oxide or cerium mixed oxide.
[0121] According to the most preferred embodiment, in one embodiment, the first proximal catalytic layer (11) and the second proximal catalytic layer (21) further contain lanthanum (La), yttrium (Y), hafnium (Hf) or a combination thereof, but preferably lanthanum, calculated as a stable oxide, in an amount ranging from 1 to 10 g / L, preferably 3 to 6 g / L, for promoting the NO of the first and second proximal catalytic layers. X and SO X Adsorption capacity.
[0122] According to the most preferred embodiment, in one embodiment, the first proximal catalytic layer (11) and the second proximal catalytic layer (21) further comprise one or more zeolites with a high Si / Al2 ratio (SAR), the zeolites being selected from β, ZSM-5, chabazite (CHA), AEI, ferrierite (Fer), Y or a combination thereof, in an amount of 5-1000 g / L, but preferably 10-50 g / L, for increasing hydrocarbons and / or NO X Adsorption capacity.
[0123] According to the most preferred embodiment, in one embodiment, in addition to the catalyst promoter, the catalytic layer (11, 12, 21, 22) includes a porous support selected from porous metal oxides, the porous metal oxides comprising aluminum oxide, aluminum oxide (Al2O3), silicon oxide (SiO X ), silicon dioxide (SiO2), titanium oxide (TiO X ), titanium dioxide (TiO2) or a mixture thereof.
[0124] According to the most preferred embodiment, in one embodiment, in all layers of the catalyst article (1), the coating amount in each coating layer is 10 to 200 g / L, preferably 40 to 100 g / L, more preferably 50 to 80 g / L, and wherein the porous metal oxide forms the balance of the coating composition.
[0125] In an embodiment, the coating comprises porous Al, Si and / or Ti oxides as carriers and promoters of active compounds for diffusion exchange with the exhaust gas passing therethrough, bringing the exhaust gas into contact with the catalytic coating.
[0126] In the present invention, the coating has its specific role in achieving the high performance of the catalyst article (1) of the present disclosure. In an embodiment, the high performance is based on the composition of each layer and zone, which has different platinum group metal (PGM) loading, Pt:Pd ratio, support composition and added promoter in the flow direction.
[0127] In a preferred embodiment, the radial (bottom layer, i.e., proximal end; top layer, i.e., distal end) and axial (inlet, middle, outlet) positions of the active compound (PGM) and promoter in different coating layers have a critical impact on the functionality and durability to avoid deactivation. In a preferred embodiment of the present invention, the front portion (inlet) of the catalyst article (1) of the present disclosure is mainly responsible for the reaction initiation and oxidation of hydrocarbons, H2 and CO.
[0128] During diesel particulate filter (DPF) regeneration, hydrocarbons having the lowest light-off temperature, such as unsaturated hydrocarbons or aromatic hydrocarbons having a medium carbon chain length, are rapidly oxidized in the front portion.
[0129] Furthermore, during DPF regeneration, hydrocarbons with the highest light-off temperatures, such as saturated hydrocarbons with significantly shorter or longer carbon chain lengths, require longer residence times, higher reaction temperatures, and Pt-rich PGM compositions, and are therefore oxidized at the rear (outlet) of the catalyst article (1).
[0130] Therefore, in a preferred embodiment of the present invention, the entire axial and radial length of the catalyst article (1) of the present invention is used for the oxidation of different types of hydrocarbons at low temperatures.
[0131] In a preferred embodiment of the present invention, the rear part of the catalyst article (1) disclosed herein is also responsible in particular for the oxidation of NO to NO2, which improves the soot oxidation in the particle filter (e.g. in the DPF) and the reduction of NO2 by ammonia or urea (NH3- or urea-SCR) or lean NO X Selective catalytic reduction of NO in LNT units X reduction.
[0132] In an embodiment, the catalyst product (1) of the present disclosure may also include a catalyst product (1) that is prepared by utilizing NO X Adsorption and storage functions as tailored structures to promote NO in intact ATS X Removal efficiency properties. NO X The storage function can be applied in the same or preferably in a different layer in which the oxidation reaction takes place.
[0133] The oxidation and adsorption functions can also be divided in two different catalyst articles (1) of the present disclosure, with specific pore densities on the substrate (2).
[0134] Specific metal oxide or zeolite compounds can be used as promoters to improve the performance of the catalyst article (1) of the present disclosure. These compounds are added to specific locations of the catalyst article (1) of the present disclosure to optimize their promoting effect.
[0135] In a preferred embodiment, tungsten (W) in the form of tungsten oxides, such as tungsten trioxide (WO3), can be used to stabilize Pt and improve the activity of the catalyst article (1) of the present disclosure in the oxidation of NO to NO2. Compared to PGM components such as platinum and palladium, tungsten (W) is a relatively cheap material and is therefore a good substitute for them.
[0136] In a preferred embodiment, silicon (Si) and / or zirconium (Zr) compounds in oxide form, such as silicon dioxide (SiO2) and zirconium oxide (ZrO2), can be used to avoid sulfur oxides (SO X ) on the catalyst product (1) of the present disclosure, and thus improve the activity and stability of the catalyst product (1) of the present disclosure during its entire life.
[0137] In a preferred embodiment, lanthanum (La), hafnium (Hf), yttrium (Y) and / or cerium (Ce) compounds in the form of oxides, such as lanthanum oxide (La2O3), yttrium oxide (Y2O5) and / or cerium dioxide (e.g., CeO2), can be used to improve nitrogen oxides (NO X ) on the catalyst product (1) of the present disclosure, thereby reducing the total NO of ATS X emission.
[0138] In a preferred embodiment, the zeolite is used as a hydrocarbon or NO on a tailored layer of the catalyst article (1). X Traps to reduce hydrocarbons and NO during engine cold start X emission.
[0139] In a preferred embodiment, the catalyst article (1) of the present disclosure, wherein the first catalytic partition (10) selectively converts hydrocarbons (HC), H2 or carbon monoxide (CO) in the exhaust gas into water and carbon dioxide, comprises at least two coatings having specific functions in removing exhaust gas components.
[0140] In a preferred embodiment, according to the main aspects and embodiments of the present invention, all or most of the platinum group metal (PGM) components in metal or oxide form, such as platinum (Pt), palladium (Pd), rhodium (Rh), iridium (Ir), ruthenium (Ru), osmium (Os) and / or precious metals such as silver (Ag) and gold (Au), but preferably PGM components, more preferably Pt and Pd are in the top layer. In contrast, according to the main aspects and embodiments, the bottom layer has a smaller amount of PGMs than the top layer, or does not contain PGM components.
[0141] The PGM loading (g / L, grams of PGM per volume of substrate, volume in liters) and the Pt:Pd ratio (mass ratio of Pt to Pd) vary over the length of the catalyst article (1). The amount of PGM component at the front (inlet) of the catalyst article (1) may be the same or higher than the amount of PGM component at the rear (outlet) of the catalyst article (1). Conversely, the Pt:Pd ratio at the outlet portion of the catalyst article (1) is the same or higher than the Pt:Pd ratio at the inlet portion of the catalyst article (1).
[0142] The PGM loading in the catalyst article (1) is primarily defined as a volume value (grams of PGM per volume of substrate, with volume in liters, g / L). The PGM loading of the entire front and back portion of the catalyst article (1) can be defined as grams of PGM per volume of the front (or back) portion of the substrate, but this is less useful.
[0143] The front part of the catalyst article (1) comprises at least two different coatings, an inlet bottom layer (In-B) and an inlet top layer (In-T), and the rear part of the catalyst article (1) comprises at least two different coatings, an outlet bottom layer (Out-B) and an outlet top layer (Out-T), e.g. Figure 1 shown.
[0144] It is also possible to define the PGM loading for each location separately for the top layer (distal end) and the bottom layer (proximal end). Figure 1-Figure 7 ), the PGM loading is in the range of about 0.5-7.0 g / L, preferably 0.5-3.0 g / L, more preferably 0.8-1.5 g / L, and the Pt:Pd ratio in the In-T coating of the catalyst article (1) is in the range of about 1:4-5:1, preferably 1:1-4:1, but more preferably 2:1-3:1.
[0145] It is important to have both Pt and Pd in the In-T coating to have a low ignition temperature (T 50 , when reaching 50% conversion), and achieving good stability to thermal and hydrothermal aging. Pt and Pd stabilize each other through close interaction, and the bimetallic Pt+Pd catalyst is better than the single PGM catalyst.
[0146] In the Out-T coating of the catalyst article (1), the PGM loading is in the range of about 0.1-2.0 g / L, preferably 0.3-1.5 g / L, more preferably 0.5-1.2 g / L, and the Pt:Pd ratio in the Out-T coating of the catalyst article (1) is in the range of about 3: 1-30: 1, preferably 4: 1-15: 1, more preferably 5: 1-10: 1. In some embodiments, palladium is not even present.
[0147] The high Pt loading in the rear part ensures high activity and durability of the NO oxidation to NO2 reaction. Optionally, the rear part of the catalyst article (1) may also be free of Pd. In the Out-T coating, the PGM loading is about the same as or preferably lower than in the In-T coating, and the Pt:Pd ratio is about the same as or preferably higher than in the In-T coating.
[0148] Below the PGM comprising the top layer, the catalyst article (1) comprises at least In-B and Out-B coatings, which can fill the corners of the square channels. The filling of the corners creates more circular flow channels, which have a relatively lower pressure drop than square flow channels with the same hydraulic diameter.
[0149] If the bottom layer contains at least one PGM, exhaust components such as hydrocarbons, CO and nitrogen oxides that diffuse through the top layer will reach the active sites in the bottom layer. When most PGMs are used for the top layer coating, mass transfer is faster and exhaust components come into contact faster on the active sites (on the PGMs). Therefore, all or most of the PGMs are located in the top layer.
[0150] In the four-layer structure of the present disclosure, the PGM loading in the coating is in the order: In-T ≥ Out-T > In-B ≥ Out-B, preferably In-T > Out-T > In-B ≥ Out-B. Although the total loading of Pt and Pd may be equal in some layers, the Pt:Pd ratio will vary to maintain the chemical differences between the four layers (In-T, In-B, Out-T, Out-B), as required by the preferred embodiment of the present invention.
[0151] The composition of the support to which the PGM and the promoter are added can vary in layers, consisting of porous metal oxides such as aluminum oxides such as alumina (Al2O3), silicon oxide (SiO X ) such as silicon dioxide (SiO2), titanium oxide (TiO X ) such as titanium dioxide (TiO2) or mixtures and compounds thereof. Possible promoters are defined for each layer separately. In the main embodiment, the main support material is alumina, which is preferably in the gamma form, having a high surface area that facilitates the distribution of active metals and promoters.
[0152] Silica and titania can be added to different layers in a customized manner to stabilize the PGM and alumina and promote certain reactions. If present, preferably TiO2 and SiO2 are present in the top layers (e.g., In-T and Out-T). TiO X and SiO X Stabilize aluminum oxide, improve sulfur durability, and promote oxidation reactions on PGM. In addition, if TiO X Preferably present in the inlet layer, SiO XIf present in the outlet layer, Ti oxide can reduce sulfur accumulation and increase sulfur recovery, which enables the catalyst article (1) used under regeneration (DPF, desulfurization) conditions to better regenerate sulfur. Silicon oxide is preferably present in the outlet layer because silicon oxide, together with alumina, has a promoting effect on the formation of NO2 on Pt-rich compositions.
[0153] Among all the layers of the catalyst product (1), the coating amount of each coating layer is in the range of about 10-200 g / L, preferably about 40-100 g / L, and more preferably about 50-80 g / L. The total coating amount of the front part and the rear part is defined by the coating amounts of In-B+In-T and Out-B+Out-T in the four coating layers, respectively.
[0154] In addition to the aluminum oxide and PGM components, any coating of the present disclosure may optionally include other components such as tungsten oxide (WO X ) and molybdenum oxide (MoO X ), preferably comprising WO at the outlet portion of the catalyst product (1) X , in order to improve the activity of the catalyst product (1) and its durability against impurities. In particular, in a preferred embodiment, WO X , such as WO 3 , is used to promote the formation of NO 2 in Pt-rich Out-T coatings, where its addition is therefore preferred.
[0155] In the portion of the catalyst preparation (1) used, the amount of tungsten oxide calculated as WO3 is in the range of about 1-30 g / L, preferably 3-10 g / L. Calculated as WO3 in the layer present, the amount of WO3 in the dry coating is about 1-30 g / L, preferably 3-10 g / L. X The amount varies in the range of 1-20 wt%.
[0156] Zirconium oxides such as zirconium oxide (ZrO2) can also be used to increase the stability of the catalyst article (1) and its resistance to sulfur oxides and increase the formation of NO2. Zirconium increases acidity, thereby reducing SO X Adsorption on alumina-based support materials. Zr can be present in all layers, but preferably, in the Out-T coating to promote and stabilize the formation of NO2 on the Pt-rich outlet portion. In the portion of the catalyst article (1) used, the amount of ZrO2 is in the range of about 1-30 g / L, preferably 3-10 g / L. The amount of ZrO2 in the dry coating varies in the range of 1-20 wt% in the layers present.
[0157] Lanthanum oxides such as lanthanum oxide (La2O3), yttrium oxides such as yttrium oxide (Y2O5) and / or hafnium oxide (HfO X ) is used to increase the NO of the catalyst product (1) X Adsorption capacity and stability.
[0158] NO X The storage function can also be applied to the catalyst article (1), preferably in its bottom (In-B and Out-B) coatings, more preferably in its Out-B coating. X Concentration of NO occurs during cold start X In adsorption, mass transfer is not important. The top layer prevents many poisons (solids, larger HC, SO2 molecules) from entering the NO X The adsorbent material is located at the bottom layer.
[0159] The oxides of La, Y, Hf and Ce are NO X In the preferred embodiment of the present disclosure, they are separated from the top layer because they often interfere with the Pt and Pd sites in the oxidation reaction when fresh or after hydrothermal aging and increase the ignition temperature. NO2 is mainly formed on the top layer with higher PGM loading and due to rapid pore diffusion, NO2 travels to the bottom layer where it is adsorbed on these adsorbents as weakly bound metal-NO X compounds or stable metal nitrates. The same metal oxides also have the ability to adsorb sulfur oxides (SO X ) characteristics, so the sulfur oxides are trapped in the layer where the PGM loading is low or zero.
[0160] When present in the portion of the catalyst preparation (1) used, La2O3, Y2O5 and (or HfO X ) in the range of about 1-10 g / L, preferably 3-6 g / L. The amount of La2O3 in the coating should vary in the range of 1-15 wt% in the layer present. Lanthanum is preferably used in the bottom layer to generate NO X and SO X adsorption capacity and improves the absolute thermal durability close to the surface of the substrate (2), which allows the good mechanical stability of the layer to be maintained even at high temperatures.
[0161] In the catalyst article (1) and preferred embodiments of the present disclosure, the top layer prevents NO from being generated during rapid exhaust heating. X From NO X Too rapid desorption on the adsorbent (diffusion and heat transfer).
[0162] In the catalyst product (1) of the present disclosure, NO X The adsorbent, such as cerium oxide, is maintained as large particles with large volume to achieve high NO Xadsorption capacity, while PGM remains as finely dispersed small particles to achieve high catalytic activity, especially Pt is known to be very resistant to poisons chemically. In contrast, during DPF regeneration, high HC concentrations are diffusion-limited for rapid access to Pt-Pd sites. Therefore, in a preferred embodiment of the present invention, it is important that the top layer has a higher PGM concentration than the bottom layer.
[0163] In a preferred embodiment of the catalyst product (1) of the present invention, the bottom coating of the catalyst product (1) may further comprise a specified cerium oxide (CeO X ), lanthanum oxide, yttrium oxide and / or hafnium oxide, which can also be stable mixed oxides. Here, the role of La, Y, Hf and Ce oxides is to increase NO X Adsorption Capacity. In some embodiments, the bottom layer may be free of Al, Ti and Si oxides, or even include only limited Ce, La, Y and / or Hf oxides or mixtures thereof with optional PGMs.
[0164] SO on these La, Y, Hf and Ce oxide adsorbents X The adsorption strength is higher than that of SO on alumina, for example X adsorption strength, which enables the selective adsorption of SO on Ce, La, Y, and Hf oxides X , keeping SO on alumina X Optionally, the basecoat layer has a low PGM loading to increase NO X Storage activity. The base coating may include Pt and Pd in a Pt:Pd ratio of about 1:9 to about 9:1.
[0165] Preferably, the bottom layer has a composition containing only Pt or Pd with a lower PGM loading (<0.8 g / L, preferably <0.4 g / L, more preferably <0.2 g / L) to enhance NO X Storage function. In addition to the gas phase NO2 diffused from the top layer, the Pt in the bottom layer is used to store NO X The oxidation of NO to NO2 is increased in situ near the adsorbent.
[0166] For optimal utilization, the NO can be designed in more detail X The location of the adsorbent material. As NO X and SO X The La, Y, Hf oxides of the adsorbent are preferably located in the In-B coating, where NO X / SO X than on Ce compounds. As NO XThe Ce oxide of the adsorbent will be preferably located in the Out-B coating where the amount of poisonous and inhibitory HC and CO is lower, the temperature during engine start-up is lower, and the NO2 concentration is higher due to the Pt-rich top layer.
[0167] When the Pt-rich layer outperforms the low Pt / Pd catalyst in the HC-SCR reaction, the formed and desorbed NO2 can be better utilized in the outlet coating. Of course, HC-SCR also takes place in the inlet layer when the HC concentration is high. When NO with a higher desorption temperature (La / Y / Hf) X When the adsorbent is at the beginning of the flow, the desorbed NO X Able to pass through the outlet zone without being adsorbed by any Ce compounds present.
[0168] If Ce is located only in the In-B layer and La / Hf / Y is located in the Out-B layer, the desorbed NO X will adsorb on the downstream La / Y / Hf sites. Therefore, in a preferred embodiment, La, Y and / or Hf are in an optimal structure located in the In-B layer, while Ce or stabilized Ce is located in the Out-B layer. However, if low temperature adsorption-desorption is the primary concern, both the In-B and Out-B coatings may contain Ce.
[0169] NO adsorbed on adsorbents (e.g. Ce, La, Y and Hf oxides, zeolites) X and SO X These compounds and PGM-zeolites have NO X Adsorption characteristics, which are based on NO at low temperatures (<200°C) X adsorption and desorption under lean exhaust conditions above 160-200°C. X It is adsorbed at low temperatures, when the downstream urea selective catalytic reduction (SCR) catalyst is not yet activated, and is desorbed at the temperature at which the SCR starts urea injection.
[0170] Application of the adsorption-desorption properties of the catalyst article (1) to achieve challenging total NO in the latest lean applications such as diesel and H2 engines X Performance target. When the adsorption-desorption characteristics are different for the PGM-rich and bottom layers, it does not interfere with the interaction of the PGMs with their optimal support. Mass transfer to the top PGM sites needs to be fast, such as DPF regeneration conditions (high HC), but under use conditions the adsorbed compounds will have more time to diffuse to the bottom layers.
[0171] In the catalyst product (1) disclosed herein, when NO X The collector also captures SO XWhen SO X Keep away from the main PGM. For the most effective application of NO X Adsorption and nitrate / NO X Regeneration (decomposition) can also be carried out on NO X / SO X The catalyst preparation (1) of the adsorbent is periodically enriched (λ<1.2, preferably <1.0).
[0172] Under these conditions, NO X It is easy to desorb above 150℃ and reduce at PGM sites. Oxides of Ce, La, Y and Hf are preferred compounds for application with enrichment of λ<1.2. X Compared with capture elements such as barium (Ba) and potassium (K), these compounds are more likely to recover NO under use and regeneration conditions. X and SO X , conventional capture elements require higher temperatures, especially for SO X break down.
[0173] However, if the enrichment strategy is very effective in the system (λ < 1.0), these types of NO X Adsorbents, for example alkaline earth metals such as strontium (Sr) and Ba, may be present in the catalyst article (1) to increase the adsorption capacity. In diesel and dual fuel applications, periodic DPF regeneration is also required, which will decompose, at least partially, the adsorbed and more strongly bound NO on the catalyst article (1) layer. X and SO X The natural way.
[0174] NO from Ce compounds X The adsorption capacity can be determined by, for example, CeO X Particle size and surface area (m 2 When Ce is added to the layer as Ce oxide particles, the original properties of the material in powder form are selected to achieve the best function. Using very high surface area materials and small particle size provides the highest NO X Adsorption capacity.
[0175] If the temperature is too high in the application, it is difficult to maintain the extreme initial surface area. However, the highest NO X The adsorption capacity of Ce oxide (Ce2) was measured by the Brunauer-Emmett-Teller (BET) method at 250 m 2 / g to 300m 2 / g range, preferably 260m 2 / g to 290m 2 / g, but more preferably about 270m2 / g, and has a specific surface area of 1 μm to 10 μm, preferably 5 μm (d 50 )'s average particle size (d 50 ).
[0176] This Ce oxide (Ce2) still has significantly higher adsorption capacity after hydrothermal (HT) aging at 700 °C for 20 h than another Ce oxide (Ce1), which has a low adsorption capacity of 140 m / s when freshly prepared. 2 / g specific surface area (BET), but greater than 11μm (d 50 ) particle size. The best adsorption capacity and release can be compared with particles larger than 200m 2 / g, preferably greater than 240m 2 / g of fresh state preparation (BET). These Ce compounds can be composed of less than 10 μm (d 50 ), preferably less than 7 μm (d 50 ) is defined by the original particle size distribution.
[0177] In addition to high surface area CeO2, soluble Ce compounds can be used in the same layer to produce small CeO X The binder acts as a binder to bind the larger solid particles together and form a mechanically durable porous layer that is well adhered to the surface of the substrate (2). Zr-stabilized Ce (ZrCe) oxide can have a high adsorption capacity and specific surface area (BET) (ZrCe has a surface area of 182 m 2 / g and 12 μm). Zr stabilization also prevents sulfur poisoning and improves thermal durability. In addition, manganese (Mn), titanium (Ti) and praseodymium (Pr) promoted cerium oxide can also be used as NO X Adsorbent material.
[0178] It is preferred to add zeolites such as beta, ZSM-5, chabazite (CHA), AEI, ferrierite (Fer), Y or combinations thereof with a high Si / Al2 ratio (SAR, 5-1000, preferably 10-50) in the bottom layer to increase hydrocarbon and / or NO at low temperatures. X Adsorption capacity. High SAR zeolites are good hydrocarbon traps and do not require additional metals.
[0179] However, NO can be chemically promoted by impregnating Pd or Pt on these zeolites, drying and calcining them before adding to the basecoat slurry. X and hydrocarbon adsorption. If used, the PGM-containing or PGM-free zeolite for hydrocarbon capture is preferably present in the In-B coating.
[0180] PGM can also be added to the basecoat slurry containing ready-made zeolites. Pd on zeolites (such as CHA, β and Fer) has NO X Adsorption properties. For NO X The adsorbed Pd-containing zeolite is preferably present in the In-B layer. The presence of Pt and / or Pd on these zeolites (e.g., β, ZSM-5) promotes and activates the adsorption of hydrocarbons on the zeolite. The concentration of PGM is in the range of 0.1-3.0 wt% of the dry zeolite weight. Preferably, Pd is added to CHA or Fer and Pt is added to β or ZSM-5.
[0181] The PGM components can be added to the base coating slurry in the form of nitrates, ammonium / ammonia compounds, chlorides, carbonates, sulfates or combinations thereof. The total amount of PGM components in the coating is about 0.1-10 wt % of the total coating amount, preferably 0.5-3 wt %. Organic and inorganic acids as well as ammonia, ammonium hydroxide and other inorganic hydroxides can be used to adjust the pH of the base coating solution to improve the activity, coatability and adhesion of the base coating. Optionally, the PGM components can be pre-added directly onto the raw material particles to ensure their high concentration and location in any layer.
[0182] Support and promoter components, such as aluminum, silicon, titanium, tungsten, cerium, zirconium, lanthanum, hafnium and yttrium as well as zeolites, can be added to the base coating separately as ready-made powders, oxides or their precursors (nitrates, carbonates, hydroxides, ammonium compounds), or by direct impregnation from precursor solutions into the catalyst article (1) layer.
[0183] The support and promoter material components may also be added to the base coating or directly to the catalyst product (1) layer in the form of their mixed oxides, such as Si-Al, Ti-Al, Zr-Al, La-Al, Si-Zr, Si-Zr-Al, Ce-Zr and Ce-Zr-Al oxides. The total amount of these materials in the catalyst product (1) is in the range of about 50-200 g / L, more preferably 100-150 g / L.
[0184] The described disclosure has high activity in hydrocarbon and CO oxidation at the front of the catalyst article (1), enabling high hydrocarbon oxidation, especially under DPF regeneration conditions (high hydrocarbon concentrations, such as >1% C1), where oxidation is inhibited by high hydrocarbons on conventional DOC or single PGM catalysts.
[0185] When the temperature rise is high during the rapid oxidation of high hydrocarbon concentrations using excess oxygen, higher Pd amounts are required to overcome this inhibition and improve thermal durability. Pt promotes the oxidation of certain hydrocarbons, improves chemical stability, such as stability to sulfur, and promotes interaction with Pd. The catalyst article (1) of the present disclosure also shows high activity in the oxidation of NO to NO2 in the rear part of the catalyst article (1).
[0186] The major part of the oxidation reaction occurs in the top coating of the catalyst article (1), preferably in the In-T coating which carries most of the PGM. Therefore, the internal mass transfer (pore diffusion) limitation is low, even though the pores of the top coating may be partially filled with deposits in long term use.
[0187] As shown experimentally, the In-T coating is more active than the Out-T coating in hydrocarbon oxidation under DPF regeneration conditions. In order to overcome the limitations of external and internal mass transfer under high hydrocarbon concentration conditions, it is necessary to use a longer (greater than 50% of the total length of the substrate (2), preferably 55%-70%) In-T coating with a specified PGM loading and Pt:Pd ratio. The longer In-T coating provides more residence time for catalysis and heat transfer in the exothermic reaction (HC / CO oxidation). If a thicker bottom layer increases the total coating amount, the back pressure increases and the radial flow distribution improves, resulting in higher hydrocarbon oxidation activity in DPF regeneration.
[0188] Thick sublayers with low / zero PGM loading and adsorbents produce higher adsorption capacities, which can be used for hydrocarbons and NO X When PGM atoms partially block NO X NO on adsorbent X Even if the length of the Out-T coating is short (less than 50% of the total length of the substrate (2), preferably 30%-45%), the short length is sufficient to allow the reaction to proceed at the rear of the catalyst article (1).
[0189] While hydrocarbons and CO are mainly oxidized in the In-T coating, the Out-T coating is designed and optimized primarily for NO oxidation. The concentration of exhaust components (NO, hydrocarbons, CO) is much lower in the rear section (Out-T coating), and the shorter length and coating amount are sufficient to achieve the target conversion under normal exhaust and DPF regeneration conditions.
[0190] In special cases, with NO X The layer of adsorbent can be used as the top layer when the main function of the catalyst product (1) is NO X During adsorption, rapid adsorption-desorption is required and the amount of poisons in the exhaust gas can be negligible.
[0191] However, the same composition in the layers of the present disclosure can be applied (e.g. Figure 2 and Figure 3). If there is a high amount of PGM in the bottom layer, the PGM loss due to corrosion is very low, which protects e.g. the SCR catalyst from PGM poisoning, especially when the ATS has no DPF (H2 engine applications).
[0192] The catalyst article (1) can be coated on ceramic and metal substrates (2). The substrate (2) is preferably a flow-through substrate (2), but a wall-flow filter structure can be applied in the catalyst article (1) design with layers.
[0193] According to the present disclosure, a monolithic catalyst substrate (2) made of ceramic or metal is preferred.
[0194] As known in the prior art, ceramic substrates (2) (honeycombs) typically have square cells, while most metal substrates (2) have sinusoidal channels. However, other channel cross-sections are possible according to the present invention, including triangles, hexagons, trapezoids or circles.
[0195] Substrates (2) suitable for use in the present disclosure have a cell density of 10-2000 cells per square inch (cpsi), but preferably, as is typical in lean and diesel applications, range from 100 to 600 cpsi. When the substrate (2) is a ceramic substrate (2), for lean and diesel applications, a wall thickness of 10 to 500 μm is preferred, more preferably 50 to 200 μm. When the substrate (2) is a metal substrate (2), the wall thickness of the substrate is 20 to 200 μm, preferably 30 to 100 μm, or more preferably 40 to 60 μm.
[0196] The catalyst article (1) is coated by spraying, dosing or dipping the base coating onto the substrate (2) and any mixture thereof to achieve the correct amount, penetration depth and layer thickness of the base coating within the catalyst article (1). Typical organic agents are used to modify the surface and slurry properties to achieve an effective coating process.
[0197] Active materials, such as Pt group metals, can be added to the basecoat slurry, or they can be post-impregnated or chemisorbed onto the catalyst article (1) substrate (2) from a precursor solution with an organic or inorganic (usually aqueous) solvent after the porous support material has been added. The PGM can be added to the raw materials before addition to the basecoat.
[0198] At the front of the catalyst article (1), the In-B coating is first coated on the surface of the uncoated portion of the catalyst article (1) (substrate (2)), and the In-T coating is coated on top of the bottom coating. At the rear of the catalyst article (1), the Out-B coating is first coated on the surface of the uncoated portion of the catalyst article (1) (substrate (2)), and the Out-T coating is coated on top of the outlet coating.
[0199] A schematic diagram of how these coatings are positioned is shown below. Figure 1 , Figures 4 to 7 As shown in these figures, s1, s2, s3, s4, s5 and s6 represent the (radial) coating thickness of the In-B, Out-B, In-T, Out-T, Mid-B and Mid-T coatings, respectively. Because the (axial) length L1, L2, L3, L4, L5, L6 of each coating can be in the range of 0-L (L1+L2+L5≤L; L3+L4+L6≤L) as shown in Figure 4 As shown, the top layer is not ideally located at the top layer of the layer at the same position (inlet, middle, outlet) in the flow direction.
[0200] If the catalyst article (1) has no intermediate coating, the lengths of the In-B and Out-B coatings (L1 and L2) are about 20%-80%, more preferably about 50%, of the total length of the catalyst article (1). Then, the lengths of the In-T and Out-T coatings (L3 and L4) are about 20%-80%, preferably 30%-70%, more preferably 40%-60% of the total length of the catalyst article (1), and L3>L4.
[0201] If a Mid-B coating is produced in the catalyst article (1), the lengths of the In-B, Mid-B and Out-B coatings are in the range of about 5% to 70%, more preferably about 33%, of the total length of the catalyst article (1). In addition, if a Mid-T coating is produced, the lengths of the In-T, Mid-T and Out-T coatings are in the range of about 5% to 70%, more preferably 20% to 50%, of the total length of the catalyst article (1).
[0202] The coating thickness of each of these layers (In-B, In-T, Out-B, Out-T) may be 1-100 μm, preferably 5-50 μm in lean and diesel applications. The total coating amount of each coating layer in all layers of the catalyst article (1) may be about 10-200 g / L (grams of coating per volume of substrate, volume unit is liter), preferably about 40-100 g / L, more preferably about 50-80 g / L. In general, the catalyst article (1) composition can be produced by any deposition method (e.g. ALE, sol-gel) and may include organic vapor precursors for defining elements.
[0203] The In-B, Out-B, In-T and Out-T coatings can also overlap each other to produce a layer in which these layers are mixed. This is one way to form additional intermediate coatings (Mid-B and Mid-T) in the catalyst article (1) ( Figure 5 ).
[0204] like Figure 5 As shown, the middle layer can also include a bottom layer (Mid-B) and a top layer (Mid-T), or as shown Figure 6 As shown, only the middle layer is included. The middle layer can also be prepared in other ways, by adding several base coating doses in the direction of the catalyst article (1), thereby forming a different composition in the middle layer than in the inlet layer and the outlet layer. Therefore, as desired for a given external design goal of the catalyst article (1) of the present disclosure, the total coating thickness / amount in the middle layer can be lower or higher than the total coating thickness / amount in the inlet layer and the outlet layer.
[0205] If an overlap is used in the preparation, a higher coating weight is produced. If no overlap is formed, instead of forming an opposing bottom or top layer from the other direction in the same coating depth, a lower coating weight is produced.
[0206] Likewise, the exit and inlet layers have different PGM loadings and Pt:Pd ratios. The total PGM loading in the middle layer can be higher or lower compared to the inlet and exit layers, either entirely or as a single bottom and top layer. The benefit of having a higher coating weight is to create a post-ignition (reaction initiation) zone with a high coating weight to balance the high heat formation.
[0207] Higher coating amounts further create pressure drops in the channels, which forces the gas to flow radially and uniformly through the channels. When high coating amounts / thicknesses are present only over short distances, the overall pressure drop increase is still lower. Possibly higher PGM loadings in the middle layer have the benefit of reaching complete oxidation of hydrocarbons and CO sooner.
[0208] Furthermore, when the inlet and outlet PGM loadings and Pt:Pd ratios are very different due to different reaction tailorings, it is possible to have intermediate compositions in between where the properties change stepwise from the inlet to the outlet composition.
[0209] Depending on the application, more emphasis can be placed on the properties of the inlet layer (high hydrocarbon oxidation activity) or the outlet layer (high NO2 formation activity), so that different catalytic results can be obtained simply by adjusting the partition size. Therefore, the variation of the length of the inlet layer, the intermediate layer and the outlet layer is a tool to optimize the performance of the catalyst article (1) in the application.
[0210] In one embodiment (see Figure 7), the catalyst article (1) of the present disclosure may further comprise a second top layer, which is located at the top layer of other coatings at the front or rear of the catalyst article (1) and comprises PGM components, preferably Pt and Pd. The length of the second top layer (if present) is in the range of 10%-100% of the total length of the catalyst article (1), preferably 20%-40%.
[0211] NO in catalyst products (1) X Adsorbent materials (mixed oxides of Ce, La, Y, Hf and Ce or mixtures of these oxides, zeolite materials) are used during the cold driving phase of engine start-up or low speed / load driving conditions. Below 100–200 °C, NO X Located in deNO X The NO is adsorbed in the cold phase of the catalyst product (1) before the device (e.g. SCR, LNT) and then desorbed due to the temperature increase (ideally about 150-250°C) under normal driving conditions. Here, the desorption temperature is low enough to release NO for the next adsorption stage. X The adsorption capacity is however high enough that for example an SCR catalyst and downstream urea dosing are already in operation.
[0212] Importantly, when the temperature during cruise varies between 100–250 °C, NO X The adsorbent is able to adsorb and desorb NO during transient driving X .
[0213] In an embodiment, NO X The adsorption compound (e.g. Ce compound with high surface area, zeolite) is therefore selected in such a way that it has these low temperature adsorption-desorption properties. Here, mixed oxides of Ce with Zr, Ti, Mn and / or Pr provide for increasing NO X Potential for adsorption capacity or stability (heat resistance, sulfur resistance).
[0214] Traditional NO X Adsorbent (e.g. Ba) and NO X The binding is too strong and desorption under driving conditions will start at too high a temperature. X can be adsorbed on these cryogenic adsorbents (e.g. Ce compounds), and the sulfate formed or the adsorbed SO X It is also easier to decompose. When aluminum silicate (zeolite) does not adsorb SO X When zeolite-based NO X Adsorbent for SO X It is durable. As we all know, Pt in SO X When Pd is combined with, for example, NO XWhen used with adsorbent materials, Pd sulfate decomposes under typical dilute conditions.
[0215] Furthermore, under DPF or typical SCR catalyst regeneration (for sulfur removal) conditions (e.g., at about 600°C), these NO X Any sulfate on the adsorbent will also decompose. X The sulfate on the adsorbent has not decomposed under dilute conditions at 600°C. Lanthanum, yttrium and hafnium convert NO X The adsorption window extends to the medium temperature range (above 200°C), which is consistent with the low temperature NO X Adsorbents (Ce compounds, zeolites) are used in combination.
[0216] In one embodiment, the catalyst article (1) of the present disclosure can be applied as a single or multiple units in an ATS to purify lean exhaust gases originating from the combustion of diesel, gasoline, natural gas, biofuels, synthetic HC blends, hydrogen, ammonia or combinations thereof (multi-fuel applications), or as part of a hybrid (electric and internal combustion engine) application.
[0217] In addition, the ATS may contain DPF, oxidation catalyst, hydrolysis, SCR and ammonia slip catalyst (ASC) units, and the catalyst product (1) unit is usually located before those other exhaust treatment units in terms of flow direction. Other ATS units, such as NO X Adsorption or special oxidation catalysts (eg for methane oxidation) may also be located before the catalyst article (1).
[0218] The present disclosure solves the obvious and implicit problems described above and below, and particularly relates to the following aspects and embodiments.
[0219] In a first aspect and embodiment, a catalyst article (1) for exhaust gas purification under lean exhaust gas conditions comprises a channel (3), the channel (3) is used to allow exhaust gas to pass through the catalyst article (1), thereby defining an inlet and an outlet of the channel for the exhaust gas, and a flow direction of the exhaust gas through the channel of the catalyst article (1), the channel (3) having a substrate (2) surface for carrying one or more catalytically active layers (11, 12, 21, 22), the catalytically active layers (11, 12, 21, 22) being used to convert at least a corresponding first and a corresponding second undesirable chemical component contained in the exhaust gas into at least a corresponding first or a corresponding second desired chemical component during the exhaust gas passing through the catalyst article (1);
[0220] - wherein at least a first and a second catalytic sub-area (10, 20) are arranged on the substrate (2), each respective catalytic sub-area (10, 20) comprising at least a respective first and a respective second catalytic layer (11, 12), (21, 22), arranged such that the first respective catalytic layer (11, 21) is close to the substrate (2) and the second respective catalytic layer (12, 22) is far from the substrate (2);
[0221] - wherein the first and second catalytic layers (11, 12, 21, 22) are each chemically different in pairs;
[0222] - wherein the first catalytic partition (10) is arranged in the channel (3) so that the exhaust gas passing through the channel (3) first encounters the first catalytic partition (10) before encountering the second catalytic partition (20); and
[0223] - wherein the second catalytic subzone (20) promotes the catalytic conversion of one of the corresponding first or second undesirable chemical components into the corresponding first or second desired chemical component, while the first catalytic subzone (10) does not substantially promote.
[0224] Another aspect of the present invention relates to a catalyst product (1) for exhaust gas purification under lean exhaust gas conditions, having a substrate surface, wherein the substrate surface has inlet and outlet coating compositions defined by the flow direction, wherein each corresponding inlet and outlet coating composition at least comprises a corresponding inlet and outlet proximal coating layer adhered to the substrate surface, and a corresponding inlet and outlet distal coating layer adhered to the corresponding inlet and outlet proximal coating layer; the corresponding coating layer comprises porous Al, Si and / or Ti oxides for diffusion exchange with the passing exhaust gas, so that the exhaust gas contacts the corresponding catalytic coating layer; wherein
[0225] a. The inlet-proximal (In-B) coating is located at the inlet of the catalyst article (1) and contains one or more catalytically active metals at a loading of less than 0.8 g / L, the catalytically active metals being selected from platinum group metals (PGM) comprising Pt, Pd, Rh, Ir, Ru, Os, or precious metals such as Ag or Au.
[0226] b. The inlet far end (In-T) coating is located at the inlet of the catalyst article (1) and contains one or more catalytically active metals at a loading of 0.5-7.0 g / L, and the catalytically active metals are selected from platinum group metals (PGM) including Pt, Pd, Rh, Ir, Ru, Os, or precious metals such as Ag or Au.
[0227] c. The outlet near-end (Out-B) coating is located at the outlet of the catalyst article (1) and contains one or more catalytically active metals at a loading of less than 0.8 g / L, and the catalytically active metals are selected from platinum group metals (PGM) comprising Pt, Pd, Rh, Ir, Ru, Os, or precious metals such as Ag or Au.
[0228] d. The outlet far-end (Out-T) coating is located at the outlet of the catalyst article (1) and contains one or more catalytically active metals in an amount of 0.1-2.0 g / L, and the catalytically active metals are selected from platinum group metals (PGM) including Pt, Pd, Rh, Ir, Ru, Os, or precious metals such as Ag or Au.
[0229] e. The outlet distal end (Out-T) coating comprises tungsten (W), molybdenum (Mo) and / or zirconium (Zr) compounds, more preferably tungsten compounds, to promote the oxidation of NO to NO2.
[0230] In one embodiment thereof, the inlet and / or outlet proximal (In-B and Out-B) coatings contain cerium (Ce) oxide or cerium mixed oxides, such as ZrCe, MnCe, TiCe, PrCe oxides or combinations thereof, to promote NO X Adsorption-desorption and NO2 formation below 200 °C.
[0231] Typically, cerium (Ce) oxides or cerium mixed oxides, such as ZrCe, MnCe, TiCe, PrCe oxides or combinations thereof, have a relative humidity of more than 140 m 2 / g, preferably higher than 200m 2 / g, more preferably higher than 230m 2 / g high surface area.
[0232] In another embodiment, cerium (Ce) oxide or cerium mixed oxide, such as ZrCe, MnCe, TiCe, PrCe oxide or a combination thereof, is in the form of solid particles having a particle size (d 50 ) is lower than 14 μm, preferably lower than 7 μm.
[0233] In yet another embodiment, the inlet and / or outlet proximal (In-B and Out-B) coatings include lanthanum (La), yttrium (Y), and hafnium (Hf), or a combination thereof, or promote NO X Adsorption.
[0234] In yet another embodiment, the inlet and / or outlet proximal (In-B and Out-B) coatings include beta, ZSM-5, CHA, Fer and AEI zeolites or combinations thereof to promote HC and NO X Adsorption.
[0235] In yet another embodiment, intermediate coatings are created between the inlet and outlet coating compositions, a mid-proximal end (Mid-B) and a mid-distal end (Mid-T).
[0236] In another embodiment, the length of the coating near the inlet and / or outlet (In-B and Out-B) is about 20%-80% of the total length of the substrate (2), more preferably about 50%; the length of the coating far from the inlet and / or outlet (In-T and Out-T) is about 20%-80% of the total length of the substrate (2), preferably about 30%-70%, more preferably 30%-70%, and the In-T layer is longer than the Out-T layer.
[0237] In yet another embodiment, among all the layers of the catalyst article (1), the coating amount of each coating layer may be about 10-200 g / L, preferably about 40-100 g / L, and more preferably about 50-80 g / L.
[0238] In another embodiment, the Pt:Pd ratio in the inlet far-end (In-T) coating is in the range of 1:4-5:1, preferably 1:1-4:1, more preferably 2:1-3:1, and the Pt:Pd ratio in the outlet far-end (Out-T) coating is in the range of 3:1-30:1, preferably 4:1-15:1, more preferably 5:1-10:1, or the Pt:Pd ratio in the Out-T coating can also be 1:0 (only Pt, no Pd).
[0239] In yet another embodiment, the inlet distal end (In-T) coating is more active than the outlet distal end (Out-T) coating in oxidation of carbonaceous components, and the Out-T coating is more active than the In-T coating in oxidation of NO to NO2.
[0240] In another aspect, the present disclosure relates to a catalyst according to any one of the above embodiments and other embodiments described herein below, which can be used to purify exhaust emissions from the combustion of diesel, gasoline, biofuels, hydrogen, ammonia, natural gas and combinations thereof, which has the ability to oxidize hydrocarbons (HC), carbon monoxide (CO), hydrogen (H2), ammonia (NH3) and nitrogen monoxide (NO), and adsorb and desorb nitrogen oxides (NOx) under normal driving conditions and under diesel particulate filter and catalyst regeneration conditions. X ), sulfur oxides (SO X ) and hydrocarbons (HC) or any combination thereof.
[0241] Example
[0242] Sample preparation - Methods
[0243] The catalyst articles (1) and reference samples of the present disclosure are prepared by adding one or more basecoat slurries in a specific order to a ceramic flow-through substrate (2) having a cell density of 400 cpsi and a wall thickness of 100 μm, or to a metal substrate (2) having a cell density of 300 cpsi and a wall thickness of 50 μm after rolling. The basecoat slurries contain platinum group metal (PGM) components (Pt and Pd), alumina, and other raw materials described in more detail in the examples.
[0244] The aluminum compound and other possible metal oxide precursors are first diluted in deionized water. The slurry is ground in a ball mill or continuous mill for several hours until the base coating slurry reaches the target particle size. The PGM components and other possible raw materials have been added with the pre-ground slurry, where water is the main liquid.
[0245] The ready-made base coating slurry is applied on the ceramic substrate (2) by dipping, dosing, pumping or blowing the base coating to have a target amount of base coating on the catalyst article (1) of the present disclosure and the reference sample. Optionally, the ready-made base coating slurry is brushed on the metal foil.
[0246] The amount of base coating was adjusted based on the amount of wet slurry and the solids content measured in the wet slurry.After each coating step, the coated catalyst article (1) of the invention and the reference sample were dried in an air stream at 60-120°C to remove excess water.
[0247] The catalyst article (1) of the present disclosure and the reference sample were calcined in a static air oven at 550°C for 1 hour between coating additions and at 550°C for 4 hours after all coating additions.
[0248] The final calcination temperature, calcination time and heating ramp can be selected based on the target properties of the precursor and basecoat slurry used to achieve good adhesion and high activity of the catalyst article (1).
[0249] For example, the final calcination temperature can be in the range of about 500° C. to about 700° C. Based on the final weight of the catalyst product (1) and the reference sample after calcination, the coating amount (g / L, grams of coating per volume of substrate, volume unit is liter) is calculated. More specifically, the differences between each catalyst product (1) and the reference sample are described in Table 1 and Examples 1-12.
[0250] Table 1. Composition, platinum group metal (PGM) loading and Pt:Pd ratio in different coatings and their average values, as well as additional components (elements) used without considering the alumina and PGM components.
[0251]
[0252]
[0253] The composition of the test samples in the experiment and Table 1 is as follows Figure 1 The general structural descriptions are detailed in , except for the single layer compositions. Therefore, for samples with the same top or bottom layer composition, it means that In-T and Out-T have the same composition, or In-B and Out-B have the same composition in the experiment.
[0254] Many of the samples in Table 1 were designed to optimize HC / CO oxidation, NO oxidation to NO2 or NO X The inlet or outlet layer composition of the catalyst article (1) is prepared by optimizing the adsorption-desorption performance of the catalyst article (1). This is a way to better observe the effect of a single variable. According to the inventors' understanding, the effect of the layered catalyst partitioning is largely the additive effect of the two or more layers present on the catalyst article (1).
[0255] Finally, samples with four different layer compositions (In-T, In-B, Out-T and Out-B coatings) were examined through the Example 12 sample to observe the overall function of the catalyst article (1) including two catalytic partitions (10, 20).
[0256] Example 1
[0257] like Figure 2 As shown, there are examples of different porous coatings on the bottom and top layers of a ceramic substrate (2) (2.5L for full-scale testing). The bottom layer coating comprises 100 wt% alumina and does not contain a PGM component. In the preparation of the coating on the top layer of the catalyst article (1), tungsten and platinum precursor materials are added to a pre-ground slurry containing alumina.
[0258] After coating, drying and calcining, the coating contained 87.9 wt% alumina, 10.6 wt% tungsten oxide (WO3) and 1.52 wt% platinum. The total PGM loading in this example was 0.88 g / L Pt, and no Pd was included in this example.
[0259] The coating composition of the inlet bottom layer (In-B) and the outlet bottom layer (Out-B) is the same. Figure 2 The structure of the inlet top layer (In-T) and the outlet top layer (Out-T) coating also have the same composition.
[0260] This example was prepared to show that W promotes NO2 formation in the Out-T coating of the catalyst article (1).
[0261] In the context of the present disclosure, the layered and coated catalyst article (1) according to Example 1 is suitable for use as the outlet zone (20) of the catalyst article (1) of the present invention.
[0262] Example 2
[0263] According to existing technology and Figure 2 A single coating containing tungsten was applied to this example (substrate (2), 2.5L for full scale testing) where tungsten and platinum precursor materials were added to a pre-milled slurry containing alumina.
[0264] After coating, drying and calcination, the coating contained 93.9 wt% alumina, 5.3 wt% tungsten oxide and 0.76 wt% platinum. The PGM loading in this example was 0.88 g / L Pt, and no Pd was included in this example. This composition can be applied in the catalyst article (1) as an example layer with W promotion.
[0265] Example 3 - Reference
[0266] The prior art reference oxidation catalyst had a single coating on a ceramic substrate (2) (2.5 L for full scale testing). The coating contained 99.2 wt% alumina and 0.76 wt% platinum. The PGM loading in this example was 0.88 g / L Pt (without Pd).
[0267] The results of Examples 1 to 3 are shown in Figure 8 In the examples, it is detailed how the oxidation of NO to NO2 is positively affected by a double layer structure, wherein the topmost layer (Example 1 and Example 2) comprises tungsten (W) and platinum and / or palladium, demonstrating the suitability of such a double layer structure as an outlet partition according to the present disclosure.
[0268] Example 4
[0269] This example has different porous coatings in the bottom and top coatings as shown in FIG. 3 on a ceramic substrate ( 2 ) (for SGB testing).
[0270] The primer coating contained 100 wt% alumina and contained no PGM components.The coating compositions of the inlet primer (In-B) and outlet primer (Out-B) coatings were identical.
[0271] The inlet top layer (In-T) coating is located at the front of the catalyst article (1) in the flow direction and contains 99.2 wt% alumina, 0.61 wt% platinum and 0.15 wt% palladium. In the outlet top layer (Out-T) base coating, tungsten and platinum precursor materials are added to a pre-ground slurry containing alumina.
[0272] After coating, drying and calcination, the Out-T coating contained 93.9 wt% alumina, 5.3 wt% tungsten oxide and 0.76 wt% platinum. The PGM loading of the front (inlet) section was 0.88 g / L PGM with a Pt:Pd ratio of 4:1. The PGM loading of the rear (outlet) section was 0.88 g / L Pt (without Pd).
[0273] The average PGM loading in this example was 0.88 g / L PGM and the Pt:Pd ratio was 9: 1. The inlet top layer (In-T) and outlet top layer (Out-T) coatings had different compositions and Pt:Pd ratios.
[0274] The catalyst product (1) example is prepared to show the promoting effect of Pt:Pd in the In-T coating on HC / CO oxidation, and the promoting effect of tungsten (W) and Pt in the Out-T coating on NO2 formation, thereby demonstrating the feasibility of having a partitioned coating structure on the catalyst product (1) disclosed herein and simultaneously promoting HC / CO oxidation and NO to NO2 oxidation.
[0275] Example 5
[0276] This embodiment has Figure 2 Different porous coatings in the bottom and top layers on a ceramic substrate (2) (used for SGB testing) are shown. The bottom layer coating comprises 100 wt% alumina and contains no PGM components. The coating compositions of the inlet bottom layer (In-B) and outlet bottom layer (Out-B) coatings are the same.
[0277] In the preparation of the top coating, tungsten and platinum precursor materials were added to a pre-ground slurry containing alumina. After coating, drying and calcination, the coating contained 93.9wt% alumina, 5.3wt% tungsten oxide and 0.76wt% platinum. The PGM loading in this example was 0.88g / L Pt and contained no Pd. The inlet top (In-T) and outlet top (Out-T) coatings also had the same composition.
[0278] This example was prepared to show that W promotes NO2 formation in the Out-T coating of the catalyst article (1).
[0279] In the context of the present disclosure, the layered and coated catalyst article (1) according to Example 5 is suitable for use as the outlet zone (20) of the catalyst article (1) of the present invention.
[0280] Example 6
[0281] This embodiment has Figure 2Different porous coatings in the bottom and top layers shown on a ceramic substrate (2) (used for SGB testing). The bottom layer coating comprises 100 wt% alumina and contains no PGM components. The coating compositions of the inlet bottom layer (In-B) and outlet bottom layer (Out-B) coatings are identical. The top layer coating is 99.2 wt% alumina, 0.61 wt% platinum and 0.15 wt% palladium. The PGM loading in this example is 0.88 g / L PGM with a Pt:Pd ratio of 4:1.
[0282] This catalyst example was prepared to demonstrate the promoting effect of Pt:Pd in the In-T coating on HC / CO oxidation in the catalyst article (1).
[0283] In the context of the present disclosure, the layered and coated catalyst article (1) according to Example 6 is suitable for use as the inlet zone (10) of the catalyst article (1) of the present invention.
[0284] Example 7
[0285] As shown in Figure 3, the catalyst article (1) has different porous coatings in the base, In-T and Out-T coatings on a ceramic substrate (2) (for SGB testing). The base coating contains 100 wt% alumina and does not contain PGM components.
[0286] The coating compositions of the inlet bottom layer (In-B) and outlet bottom layer (Out-B) coatings are the same. The inlet top layer (In-T) coating is located at the front of the catalyst article (1) in the flow direction and comprises 99.2 wt% alumina, 0.61 wt% platinum and 0.15 wt% palladium. In the outlet top layer (Out-T) coating, tungsten and platinum precursor materials are added to a pre-ground slurry comprising alumina.
[0287] After coating, drying and calcination, the Out-T coating contained 93.9wt% alumina, 5.3wt% tungsten oxide and 0.76wt% platinum. The PGM loading of the front section was 0.88g / L PGM, and the Pt:Pd ratio was 4:1. The PGM loading of the rear section was 0.88g / L Pt, and this section did not contain Pd. The average PGM loading in this example was 0.88g / L PGM, and the Pt:Pd ratio was 9:1. Therefore, the inlet top layer (In-T) and outlet top layer (Out-T) coatings have different compositions and Pt:Pd ratios.
[0288] This catalyst article (1) example was prepared in order to demonstrate the promoting effect of Pt:Pd in the In-T layer on HC / CO oxidation and the promoting effect of W and Pt in the Out-T coating on NO2 formation, showing the possibility of partitioning these two catalytic processes onto the same catalyst article (1) in the context of the present invention.
[0289] Example 8
[0290] The reference example has different porous coatings in the base layer, In-T and Out-T coatings on the ceramic substrate (2) (for SGB test) as shown in FIG. 3 .
[0291] The bottom coating layer comprises 100 wt% alumina and contains no PGM components. The coating compositions of the inlet bottom (In-B) and outlet bottom (Out-B) coating layers are the same. The inlet top (In-T) coating layer is located at the front of the catalyst article (1) in terms of flow direction and comprises 99.2 wt% alumina, 0.61 wt% platinum and 0.15 wt% palladium.
[0292] The outlet top layer (Out-T) coating is located at the rear of the catalyst article (1) in terms of flow direction and contains 99.5wt% alumina, 0.68wt% platinum and 0.08wt% palladium. The PGM loading at the front is 0.88g / L PGM, and the Pt:Pd ratio is 4:1. The PGM loading at the rear is 0.88g / L PGM, and the Pt:Pd ratio is 9:1. The average PGM loading in this example is 0.88g / L PGM, and the Pt:Pd ratio is 5.7:1. Therefore, the inlet top layer (In-T) and the outlet top layer (Out-T) coating have different compositions and Pt:Pd ratios.
[0293] This example was prepared to show the effect of Pt:Pd ratio on HC / CO / NO oxidation in In-T and Out-T coatings in the absence of W.
[0294] Example 9
[0295] The catalyst article (1) has different porous coatings in the base layer, In-T and Out-T coatings on a ceramic substrate (2) (for SGB testing) as shown in FIG. 3 .
[0296] The bottom coating layer comprises 100 wt% alumina and contains no PGM components. The coating compositions of the inlet bottom (In-B) and outlet bottom (Out-B) coating layers are the same. The inlet top (In-T) coating layer is located at the front of the catalyst article (1) in terms of flow direction and comprises 99.2 wt% alumina, 0.51 wt% platinum and 0.25 wt% palladium.
[0297] In the outlet top layer (Out-T) base coating, tungsten and platinum precursor materials are added to a pre-ground slurry containing alumina. After coating, drying and calcination, the Out-T coating contains 93.9wt% alumina, 5.3wt% tungsten oxide and 0.76wt% platinum. The PGM loading at the front is 0.88g / L PGM, and the Pt:Pd ratio is 2:1. The PGM loading at the rear is 0.88g / L Pt (without Pd). The average PGM loading in this example is 0.88g / L PGM, and the Pt:Pd ratio is 5:1. Therefore, the inlet top layer (In-T) and outlet top layer (Out-T) coatings have different compositions and Pt:Pd ratios.
[0298] This catalyst article (1) example was prepared to show the promoting effect of Pt+Pd in the In-T layer on HC / CO oxidation, and the promoting effect of W and Pt in the Out-T coating on NO2 formation.
[0299] Example 10
[0300] This embodiment has different porous coatings in the base layer, In-T and Out-T coatings on a ceramic substrate (2) (for SGB testing) as shown in FIG. 3 .
[0301] The primer coating contained 100 wt% alumina and contained no PGM components.The coating compositions of the inlet primer (In-B) and outlet primer (Out-B) coatings were identical.
[0302] The inlet top layer (In-T) coating is located at the front of the catalyst article (1) and contains 99.2 wt% alumina, 0.51 wt% platinum and 0.25 wt% palladium. The Out-T coating contains 99.2 wt% alumina and 0.76 wt% platinum. The PGM loading at the front is 0.88 g / L PGM with a Pt:Pd ratio of 2:1. The PGM loading at the rear is 0.88 g / L Pt (without Pd).
[0303] The average PGM loading in this example was 0.88 g / L PGM and the Pt:Pd ratio was 5: 1. Therefore, the inlet top layer (In-T) and outlet top layer (Out-T) coatings had different compositions and Pt:Pd ratios.
[0304] This example was prepared to show the effect of Pt:Pd ratio on HC / CO / NO oxidation in In-T and Out-T coatings in the absence of W.
[0305] Examples 11a-k
[0306] These embodiments have Figure 2Different porous coatings in the bottom and top coatings on the ceramic substrate (2) (for SGB testing) are shown. The bottom coating contains Pt-Ce1 (Examples 11a-b), Ce1 (11c), Pt-ZrCe-La (11d), Pt-ZrCe (11e), Pd-Fer (11f) and Pt-alumina (coded as Pt / Al, (11g), Pt-Ce2 (11h-i) and alumina (11j-k). Ce1 and Ce2 are added as ready-made powders: Ce1 is 149 m 2 / g,d 50 11μm; Ce2 is 270m 2 / g,d 50 5μm; ZrCe, 182m 2 / g,d 50 12 μm. Cerium nitrate is used as a binder and additional NO together with other Ce materials. X Source of adsorbent.
[0307] However, it can be seen that alumina sol or other binders can also be used as binders. Thus, the Ce1 and Ce2 bottom layers contain only Ce, while the ZrCe layer contains Ce and Zr. Under the conditions of use, Ce, La, ZrCe are present in the form of their stable oxides or mixtures thereof (e.g., CeO2, La2O3, ZrO2, usually CeO X 、LaO X 、ZrO X ) in the coating. La is added in the form of lanthanum nitrate solution, and Zr is added in the form of zirconium nitrate solution, so that Zr and La are well dispersed on other porous materials.
[0308] Therefore, the 11d sample consists of Zr, Ce and La in the final layer. The exact oxidation state of the metal oxides depends on the temperature and gas composition during preparation and use. These compounds can also form aluminates in the presence of aluminum oxides.
[0309] In each separate example, the coating compositions in the inlet bottom layer (In-B) and outlet bottom layer (Out-B) coatings are the same. Example 11a, b, d, e, g, h, i contain 0.15 wt% platinum, Example 11f contains 0.15 wt% palladium, and Example 11c, j, k contains no PGM in the inlet and outlet bottom layers. In each separate example, the inlet top layer (In-T) and outlet top layer (Out-T) coatings have the same composition. Example 11a, c, d, e, g, i, j contain 0.76 wt% platinum and 5.3 wt% tungsten oxide, and Example 11b, f, h, k contain 0.61 wt% platinum and 0.15 wt% palladium. The total PGM loading of Example 11a, b, d, e, f, g, h, i is 1.06 g / L PGM, while the total PGM loading of Example 11c, j, k is 0.88 g / L PGM.
[0310] In the context of the present disclosure, Example 11 illustrates the possibility of variation in the desired chemical properties of the outlet partition (Examples 11a, c, d, e, g, i, j) in the presence of tungsten (W), as well as comparative examples of the prior art (Examples 11b, f, h, k) applicable to the chemical properties of the inlet partition.
[0311] Example 12a-d
[0312] These catalyst products (1) of the present disclosure have the following characteristics: Fig.17 Four different coating compositions are shown in In-T, In-B, Out-T and Out-B coatings on ceramic substrate (2) (for SGB testing).
[0313] These inlet and outlet layers were prepared by the materials and methods described in Example 11. The In-B coating contained Pt-Ce2 (12a-b), Pd-Fer (12c) and alumina (12d), and the coating contained 0.15wt% platinum (Examples 12a, B) or 0.15wt% palladium (Example 12c) or no PGM (Example 12d). The Out-B layer contained Pt-Ce2 (12a, c), alumina (12b, d), and the coating contained 0.15wt% platinum (Examples 12a, c) or no PGM (Examples 12b, d). Therefore, Example 12d is comparable to Examples 12a-c.
[0314] The In-T coating contained 0.61 wt% platinum and 0.15 wt% palladium (Examples 12a-d). The Out-T coating contained 0.76 wt% platinum and 5.3 wt% tungsten oxide (Examples 12a-d). The total PGM loading of Examples 12a and c was 1.06 g / L PGM, the total PGM loading of Example 12b was 0.97 g / L PGM, and the total PGM loading of Example 12d was 0.88 g / L PGM. The inlet top layer (In-T) and outlet top layer (Out-T) coatings in each individual example had different compositions and Pt:Pd ratios. The inlet bottom layer (In-B) and outlet bottom layer (Out-B) coatings in the examples had different compositions and PGMs.
[0315] These catalyst articles (1) were prepared to demonstrate the promotion of HC / CO oxidation by Pt+Pd in the In-T layer, the promotion of NO2 formation by W and Pt in the Out-T coating, and the promotion of NO2 formation by W and Pt in the bottom layer. X Removed NO X Adsorption-desorption properties.
[0316] Activity Measurement - Test
[0317] Test Method
[0318] The catalytic activity of small cylindrical test size samples (14 mm in diameter and 75 mm in length) was investigated by syngas bench (SGB) experiments. The test size samples were cut from full size ceramic substrates (2) (1.2 dm in the example). 3 ) or rolled from the coated metal foil and then placed in a tubular metal tube reactor. 1) fresh samples, or 2) samples after hydrothermal aging (HT) at 700°C for 20 hours (H2O vapor concentration during aging was 10 vol%), or 3) samples after hydrothermal aging (HT) at 700°C for 20 hours + sulfur dioxide (SO2) aging at 400°C for 20 hours (SO2 concentration during aging was 25 ppm) were tested.
[0319] The activity of the samples was studied in light-off tests with two gas mixtures simulating the composition of diesel exhaust: 1) a normal gas mixture ( Fig.10 referred to as "normal" in the 10 H 22 (decane), 10ppm C7H8 (toluene), 40ppm C3H6 (propylene), 300ppm CO, 500ppm NO, 10% O2, 6% H2O, 6% CO2, balance nitrogen (N2), space velocity (SV) is 50.000h -1 ; 2) Regeneration gas mixture (in Fig.10The gas was named "reg" in the above text and consisted of 4000ppm C3H6, 2000ppm CO, 200ppm NO, 6% O2, 6% H2O, 6% CO2, and the balance N2, with a space velocity of 50.000h -1 .
[0320] The activity of the samples was tested in THC oxidation, the light-off temperature of THC (the temperature at which 50% THC conversion is reached), and the oxidation of NO to NO2 during the light-off test.
[0321] Also in NO X The activity of the SGB test samples was investigated in adsorption / desorption experiments. The investigated samples were first pretreated with a gas mixture containing 13% O2, 6% H2O and the balance N2 at 500°C for 10 minutes and then cooled to 120°C in the same gas mixture. The NO adsorption stage was carried out at 120°C in a gas mixture containing 100 ppm NO, 13% O2, 6% H2O and the balance N2.
[0322] Then, NO X The desorption phase was carried out by heating the sample from 120°C (10°C / min) to 500°C in a gas mixture containing 6% H2O and the balance N2. The space velocity was 50.000 h / min during the entire test phase. -1 .
[0323] Based on NO X NO measured during adsorption and desorption X Quantity definition NO X Adsorption capacity (μmol / g 涂层 ). NO X The adsorption on the catalyst surface and the adsorbent can be physical or chemical, for example in the form of nitrates or nitrites or their precursors.
[0324] NO detected by desorption X The adsorption capacity involves more strongly bound NO than that detected by the step exchange method. X . NO X The release with temperature directly shows the adsorption strength, which is based on NO X Adsorption control of NO X An important property of.
[0325] The total adsorption capacity is calculated by desorption of NO at 120-500 °C. X In addition, it is also calculated based on low-temperature desorption in the range of 120-200 °C. X (0-1.0 or 0-100%) is based on the desorption of NO before the sample reaches a certain temperature (e.g. 200°C) XThe ratio of (accumulated) and NO desorption during the heating stage X is defined by the total amount.
[0326] Full-scale specimens (2.5 dm in the example) were investigated in diesel engine tests under steady-state conditions. 3 ) were studied as fresh samples or as well as as 2) samples after hydrothermal aging at 700°C for 5 h (with a H2O vapor concentration of 10 vol% during aging).
[0327] In the engine test, the exhaust gas from Agco Sisu 4.9L was used, with airspeeds of 50.000-250.000h -1 , depending on engine speed and torque. During steady-state tests, the activity of the samples in the oxidation of NO2 by NO was investigated. More precisely, Figure 8-Figure 17 The test results for each SGB and diesel engine test are described in Tables 2-3.
[0328] Test Results
[0329] Figure 8 Test results in
[0330] The activity of the fresh catalyst product (1) of Example 1, the coating composition of Example 2 and the reference catalyst of Example 3 was investigated in a steady-state engine test. Figure 8 shown.
[0331] The results of Examples 1, 2 and 3 in terms of oxidation of NO to NO2 are different from each other. At 220-380°C, the oxidation of NO to NO2 of the layered sample containing W+Pt (Example 1) is 6%-14% higher than that of the single-layer sample containing Pt (Example 3). At 220-380°C, the oxidation of NO to NO2 of the single-layer sample containing W+Pt (Example 2) is 3%-6% higher than that of the single-layer sample containing Pt (Example 3).
[0332] The results clearly show the promoting effect of tungsten and the bilayer structure on NO2 formation compared with the single layer sample without tungsten.
[0333] Fig. 9 Test results in
[0334] The activity of the catalyst preparations (1) of Examples 4 and 5 and the reference catalyst of Example 6 hydrothermally aged at 700°C (HT700) was investigated in a light-off test in a synthesis gas bench (SGB). Fig. 9 The results of the examples differ from each other in terms of the oxidation of NO to NO2. The results are presented regarding the effect of tungsten and zone coatings on the investigated catalyst articles (1).
[0335] According to this embodiment, at 210-350°C, the oxidation of NO to NO2 on the samples with Pt+Pd in the In-T coating and W+Pt in the Out-T coating (Example 4) and the sample with W+Pt in the top layer (Example 5) is 7%-20% higher than the oxidation of NO to NO2 on the sample with Pt+Pd in the top layer (Example 6).
[0336] The results show that using W+Pt instead of Pt+Pd in the Out-T coating improves the formation of NO2.
[0337] Fig.10 Test results in
[0338] The activity of the catalyst preparations (1) of Examples 4 and 5 and the reference catalyst of Example 6 aged at HT700 was investigated in a light-off test in a synthesis gas bench (SGB). Fig.10 The catalyst article (1) examples differ from each other in terms of THC light-off temperature. Results are presented regarding the effects of tungsten and zone coatings on the catalyst articles (1) studied.
[0339] According to this embodiment, under normal gas mixture, the THC ignition temperature of the layered sample with Pt+Pd in the In-T coating and W+Pt in the Out-T coating (Example 4) and the sample with Pt+Pd in the top layer (Example 6) is 4-12°C lower than the THC ignition temperature of the sample with W+Pt in the top layer (Example 5). Under regeneration gas mixture, the THC ignition temperature of the samples of Example 4 and Example 6 is 26-32°C lower than the THC ignition temperature of Example 5.
[0340] The results indicate that the use of Pt+Pd in the In-T coating is required for high THC oxidation activity at low temperatures.
[0341] Fig.11 Test results in
[0342] The activity of the catalyst preparation (1) of Example 7 and the reference catalyst of Example 8 hydrothermally aged at 700°C (HT700) was investigated in a light-off test in a synthesis gas bench (SGB). The results on the effect of tungsten and Pt:Pd ratio on the catalyst preparation (1) are shown in Figure 1. Fig.11 As displayed.
[0343] According to this embodiment, the sample with Pt+Pd in the In-T coating and W+Pt in the Out-T coating (Example 7) is able to achieve the same NO oxidation to NO2 as the sample with Pt+Pd in the In-T and Out-T coatings (Example 8), demonstrating the effectiveness of using tungsten as a cheaper alternative to platinum and palladium in the NO to NO2-oxidation catalyst product (1).
[0344] The results show that samples with high Pt:Pd ratio in Out-T coatings have the same NO2 formation as samples with W+Pt when HT aged.
[0345] Fig.12 Test results in
[0346] The activity of the catalyst preparation (1) of Example 7 and the reference catalyst of Example 8 after hydrothermal aging at 700°C for 20 hours and SO2 aging at 400°C for 20 hours was investigated in a light-off test in a synthesis gas bench (SGB). The results on the effect of tungsten and Pt:Pd ratio on the catalyst preparation (1) are shown in Figure 1. Fig.12 As displayed.
[0347] According to this embodiment, at 220-360°C, the oxidation of NO to NO2 on the samples with Pt+Pd in the In-T coating and W+Pt in the Out-T coating (Example 7) is 10%-18% higher than the oxidation of NO to NO2 on the samples with Pt+Pd in the In-T and Out-T coatings (Example 8).
[0348] The results show that the use of W+Pt in the Out-T coating gives good sulfur resistance compared to the Pt+Pd sample (even with a high Pt:Pd ratio).
[0349] Fig.13 Test results in
[0350] The activity of the catalyst preparation (1) of Example 7 and the reference catalyst of Example 8 after hydrothermal aging at 700°C for 20 hours and / or SO2 aging at 400°C for 20 hours was investigated in a light-off test in a synthesis gas bench (SGB). The results on the influence of tungsten and Pt:Pd ratio on the investigated catalyst preparation (1) are shown in Figure 2. Fig.13 As displayed.
[0351] According to this embodiment, under a normal diesel exhaust mixture, the sample with Pt+Pd in the In-T coating and W+Pt in the Out-T coating (Example 7) can reach the same THC light-off temperature (T ) as the sample with Pt+Pd in the In-T and Out-T coatings (Example 8). 50 ).
[0352] The results show that under the conditions studied, using W+Pt or Pt+Pd in the Out-T coating gave the same THC oxidation activity.
[0353] Fig.14 Test results in
[0354] The activity of the catalyst preparation (1) of Example 9 and the reference catalyst of Example 10 aged at HT700 was investigated in a light-off test in a synthesis gas bench (SGB). The results regarding the effect of tungsten on the investigated catalyst preparation (1) are shown in Table 1. Fig.14 As displayed.
[0355] According to this embodiment, at 230-380°C, the oxidation of NO to NO2 on the sample with W+Pt in the Out-T coating (Example 9) is 8%-12% higher than the oxidation of NO to NO2 on the sample with only Pt in the Out-T coating (Example 10).
[0356] The results show that W promotes NO2 formation on the samples studied.
[0357] Fig.15 Test results in
[0358] The activity of the catalyst preparation (1) of Example 9 and the reference catalyst of Example 10 aged at HT700 was investigated in a light-off test in a synthesis gas bench (SGB). The results regarding the effect of tungsten on the investigated catalyst preparation (1) are shown in Table 1. Fig.15 exhibit.
[0359] According to this embodiment, under a normal diesel exhaust mixture, the sample with Pt+Pd in the In-T coating and W+Pt in the Out-T coating (Example 9) reaches the same THC light-off temperature (T ) as the sample with only Pt in the Out-T coating (Example 8). 50 ) and 4°C higher CO ignition temperature.
[0360] The results show that W has little effect on the oxidation activity of CO and THC on samples containing Pt (without Pd) in the Out-T coating.
[0361] Fig.16 And the test results in Table 2—NO X Adsorption and desorption capacity
[0362] The activity of the fresh two-layer catalyst composition of Examples 11a-g in the synthesis gas test bed (SGB) was X These catalyst compositions simulate various inlet and outlet compositions in the catalyst preparation (1). X Before the adsorption step, the catalyst was treated at 500 °C under dilute conditions. X The adsorption capacity from the results of the desorption stage is shown in the next table.
[0363] Using this embodiment, by adding NO XAdsorbent (Ce, ZrCe, La, with or without Pt; or Pd zeolite), NO X The adsorption capacity was improved (Table 2). This improvement was achieved even if the top layer contained only PGM, Al oxide and possibly W, but the adsorption capacity was calculated over the combined weight of the bottom and top layers. If the alumina was used only as support, the adsorption capacity was 9 (w / o Pt) or 19 μmol / g of coating material.
[0364] The results show that at a low temperature of 120°C, the presence of Pt in the Ce layer has an important effect on the NO X Adsorption capacity is promoted. Low concentrations of in situ NO2 generation at Pt sites near the bottom Ce adsorbent have a promoting effect. Adding Ce1 to the bottom layer with or without Pt / Pt+Pd increases the adsorption capacity to 37-58 μmol / g (2-5 times higher), even if only the bottom layer is the main adsorption layer.
[0365] The use of Zr-stabilized Ce oxide (ZrCe) resulted in 33-50 μmol NO X / g, palladium ferrous zeolite leads to 19μmol NO X / g. Pt-only type is used for outlet partitions, and Pt+Pd type is used for inlet partitions. X Adsorbents as a coating can maximize adsorption capacity, but the present disclosure is intended to optimize the catalyst article (1) for oxidation reactions in normal use or DPF regeneration and for passive NO X Adsorption-desorption.
[0366] Due to component interactions and undesirable mass transfer limitations, all components (PGM, NO X The presence of adsorbents, W) will lead to negative effects such as lower thermal / sulfur durability, lower Pt stability, lower NO X Adsorption capacity.
[0367] These results apply to typical lean applications such as exhaust combustion with diesel, natural gas, and / or hydrogen fuels. These compositions act as a passive NO X The adsorbent releases NO when the temperature rises to about 180-250°C. X .
[0368] Table 2: NO desorption of the double-layer catalyst alone at 120-200 °C by programmed temperature desorption experiments in the range of 120-500 °C. X Adsorption capacity and desorption.
[0369]
[0370] According to the desorption results at 120-500 °C, even the porous alumina commonly found in conventional DOCs has a low adsorption capacity, but NO X The binding on the surface was tighter (Table 2, Fig.16 ). Below 200℃, NO on alumina X Low desorption (11% desorption), which is not suitable for downstream deNO X In contrast, at up to 200 °C, catalysts containing cerium (Ce1), lanthanum and Pd-Fer released 36%-43% of the adsorbed NO X .
[0371] Even though the Pd-Fer-containing samples have lower NO X Adsorption capacity, at 200℃, NO X The catalyst composed of ZrCe+La has a fairly good release, but the La nitrate is more stable than the nitrate on cerium oxide, resulting in a moderate adsorption strength and NO release at higher temperatures. X Desorption.
[0372] At 270-380 °C, La and Ce oxides have stronger binding properties than alumina to nitrate (NO X ), but due to its three times higher capacity, it prevents NO X The buffering effect of NO emissions is much higher than that of aluminum oxide. X La is good in combination with cerium materials for discharge. High surface area (>200m 2 / g)Ce2 as NO X The adsorbent significantly increased the NO X Adsorption capacity is as high as 88-108μmol / g.
[0373] In addition, below 200 °C, the NO X The release is also very high, up to 49%-59%. In the range of 120-200℃, the desorbed NO X The major part (>50%) of the NO is also NO2, which will have a positive effect on NH3-SCR, HC-SCR and HC oxidation reactions at these low temperatures. X The desorption on the adsorbent can even form NO2 into the exhaust gas stream at a lower temperature than the Pt-rich top layer or conventional DOC. This is due to the NO in the catalyst preparation (1). X Adsorption-desorption. These passively absorb NO under dilute conditions X and the ability to effectively oxidize HC, CO and NO emissions results in a comprehensive solution having the desired properties in a layered catalyst article (1).
[0374] Such a catalyst article (1) can be helpful for SCR catalysts, especially under cold driving conditions, such as in the World Harmonized Transient Cycle (WHTC) under cold start conditions, where the temperature is mainly below 200°C in the first 400 seconds. X The adsorption-desorption utilization can be evaluated by an example of a 4.4L diesel engine, where the total raw NO in this cycle (4.7g / kWh) X The emission is about 50 grams. The whole system utilizes NO X Adsorption-desorption, wherein an effective SCR catalyst (e.g. based on Cu zeolite) is located after the catalyst article (1), and the desorbed NO X is reduced at the SCR operating temperature.
[0375] When the volume is 3.4dm 3 , the coating amount is 140 g / L and the total adsorption capacity is about 100 μmol NO X When the catalyst article (1) having 100 g of coating (by way of Examples 11h and 11i) is used as an example, the total adsorption capacity will be about 2.2 g NO2 (at 120°C).
[0376] Therefore, it is roughly estimated that when the temperature cycle is in the range of 50-250℃ and NO X The adsorption capacity can be used 1-3 times in the adsorption-desorption cycle, and it is possible to remove about 1-3 grams of NO2 in the first 500 seconds. When the auxiliary SCR system is in the cold stage below 180°C and the urea / NH3-SCR is not yet activated, the NO2 of the catalyst article (1) X The removal potential is significant.
[0377] In cold WHTC, NO X The conversion rate during the entire cycle is usually maintained below 90%. The catalyst preparation (1) provides a X The conversion rate can be increased by 2%-6%, which is significant for the total NO X The removal efficiency is substantially improved.
[0378] The test results in Table 3
[0379] Activity of fresh catalyst preparation (1) of Examples 11a-d in NO in a synthesis gas test bed (SGB) X The results of these four-layer catalyst preparations (1) are shown in Table 3. Ce2 is a high surface area CeO X compounds, with small particle size and high NO XThe highest NO adsorption capacity was achieved when both the inlet and outlet layers contained Ce2 (Example 12a). X Adsorption capacity. In the temperature range of 120-200℃, NO X The release of NO was also high. Using Pd-Fer as the bottom layer and Pt+Pd+Al as the top layer in the inlet part (Example 12c) also showed high NO X Adsorption capacity. At 120-200℃, no NO X The reference adsorbed compound (Example 12d) clearly showed lower NO X Adsorption capacity and relatively low NO X When four layers are used in the catalyst article (1), a combinatorial boost is achieved.
[0380] At 120-200°C, the absolute NO X Desorption is 5-8 times higher than using alumina-based references. X Compared with the adsorbents, Pd-zeolite has lower NO X adsorption capacity, but has better NO at low temperatures X Release the ability. Except NO X In addition to adsorption, Pd-zeolite also plays a role in HC trapping and oxidation to reduce HC emissions during normal driving at low temperatures (<200°C) or during DPF regeneration.
[0381] When calculating the total coating amount NO in this embodiment X Adsorption capacity, including no NO X Layer of adsorbent material, containing Ce2 NO X NO in the adsorbent layer X The adsorption capacity can be estimated to be about 100-150 μmol / g. X The coating amount of the adsorbent layer is used to adjust the NO X Adsorption capacity. If NO is required at extremely low temperatures around 100-120°C X Adsorption capacity, a relatively high PGM loading can be used on the top or bottom layer to promote more NO conversion to NO2 on the catalyst surface.
[0382] Table 3: NO desorption of the four-layer catalyst at 120-200 °C by programmed temperature desorption experiments in the range of 120-500 °C. X Adsorption capacity and desorption.
[0383]
[0384]
[0385] Fig.17 Test results in
[0386] Corresponding to the previous test graphs, the activity of the same catalyst preparations (1) of fresh examples 12a, 12b and 12d was investigated in a light-off test in a synthesis gas test bench (SGB). The influence of these combinations on the NO2 formation is shown in FIG. Fig.17 As displayed.
[0387] According to this embodiment, all NO X NO at different locations of the adsorbent sample X The adsorbent material was able to achieve the same activity for oxidation of NO to NO2. In addition to these tests, HT700 aged Examples 12a, 12b and 12d were studied under regeneration conditions, where it can be seen that the THC light-off temperature of these examples is smaller (within 5°C). The results confirm that the Ce compound in the bottom layer has a minor effect on NO2 formation and THC conversion on the catalyst article (1).
[0388] The best mode according to the present disclosure is given by the examples, wherein the inlet / outlet of the catalyst article (1) is given by Examples 12a-c. In these combinations, the following features are used:
[0389] -Layered structures with optimized PGM utilization and coating composition;
[0390] - Export tungsten in the distal layer to promote NO2 formation and increase stability against sulfur poisoning;
[0391] - Bottom layer NO X Adsorption-desorption characteristics enhance DeNO in cold start X Function;
[0392] - NO in the inlet and outlet bottom (proximal) coating X Adsorption-desorption characteristics to achieve high NO X Adsorption and desorption, thus promoting deNO in cold start X The overall NO in the unit X removal while still ensuring high NO2 formation and efficient HC oxidation under DPF regeneration conditions.
[0393] The main inventive step is to combine the layered structure design with tungsten doping in the top layer of the outlet and NSC material in the bottom layer to form a high NO X Adsorption-desorption and high NO2 formation are combined with high thermal and sulfur resistance. These embodiments are combined with PGM loading in the washcoat and Pt:Pd ratio optimization to achieve high efficiency of DPF active regeneration also at high HC concentrations.
[0394] End Comments
[0395] Although the invention has been described in detail for purposes of illustration, it should be understood that such details are for illustrative purposes only and variations may be made thereto by one skilled in the art in practicing the claimed subject matter, upon study of the drawings, the disclosure, and the appended claims.
[0396] The term "comprising" used in the claims does not exclude other elements or steps. The indefinite article "a" or "an" used in the claims does not exclude a plurality. A single processor or other unit may fulfill the functions of several means recited in the claims. Reference signs used in the claims should not be construed as limiting the scope.
Claims
1. A catalyst product (1) for exhaust gas purification under lean exhaust gas conditions, comprising a channel (3), the channel (3) being used to allow exhaust gas to pass through the catalyst product (1), thereby defining an inlet and an outlet of the channel for the exhaust gas, and a flow direction of the exhaust gas through the channel of the catalyst product (1), the channel (3) having a substrate (2) surface for carrying one or more catalytically active layers (11, 12, 21, 22), the catalytically active layers (11, 12, 21, 22) being used to convert at least a corresponding first and a corresponding second undesirable chemical component contained in the exhaust gas into at least a corresponding first or a corresponding second desired chemical component during the exhaust gas passing through the catalyst product (1); - wherein at least a first and a second catalytic partition (10, 20) are arranged on the substrate (2), each corresponding catalytic partition (10, 20) comprising at least a corresponding first and a corresponding second catalytic layer (11, 12), (21, 22), arranged such that the first corresponding catalytic layer (11, 21) is close to the substrate (2), and the second corresponding catalytic layer (12, 22) is far from the substrate (2); - wherein the first and second catalytic layers (11, 12, 21, 22) are each chemically different in pairs; - wherein the first catalytic partition (10) is arranged in the channel (3) so that the exhaust gas passing through the channel (3) first encounters the first catalytic partition (10) before encountering the second catalytic partition (20); and - wherein the second catalytic subzone (20) promotes the catalytic conversion of one of the corresponding first or second undesirable chemical components into the corresponding first or second desired chemical component, whereas the first catalytic subzone (10) does not substantially promote.
2. The catalyst product (1) according to claim 1, wherein in the flow direction of the exhaust gas through the channel (3), at least a third partition (30) is arranged in the channel (3) after the first catalytic partition (10) and before the second catalytic partition (20).
3. A catalyst product (1) according to any one of the preceding claims, wherein the first catalytic partition (10) selectively converts hydrocarbons, H2 and / or carbon monoxide (CO) in the exhaust gas into water and carbon dioxide; and the second catalytic partition (20) selectively converts nitrogen monoxide into nitrogen dioxide, and / or converts sulfur dioxide into sulfur trioxide.
4. The catalyst product (1) according to claim 3, wherein the first catalytic partition (10) contains one or more catalytically active metals selected from platinum group metals (PGM) including Pt, Pd, Rh, Ir, Ru, and Os at a metal loading of less than 0.8 g / L in the first proximal catalytic layer (11); and contains one or more catalytically active metals selected from platinum group metals (PGM) including Pt, Pd, Rh, Ir, Ru, and Os at a metal loading of 0.5-7.0 g / L in the first distal catalytic layer (12), provided that the metal loading in the first distal catalytic layer (12) should be higher than the metal loading in the first proximal catalytic layer (11).
5. The catalyst article (1) according to claim 4, wherein the platinum group metal selected for the first proximal catalytic layer (11) and the first distal catalytic layer (12) is platinum and / or palladium.
6. The catalyst article (1) according to claim 5, wherein platinum and palladium are present in the first distal catalytic layer (12) in a Pt:Pd ratio ranging from 1:4 to 5:1, and are present in the first proximal catalytic layer (11) in a Pt:Pd ratio ranging from 1:9 to 9:
1.
7. The catalyst article (1) according to claim 3, wherein the second catalytic partition (20) comprises one or more catalytically active metals selected from the group consisting of platinum group metals (PGM) including Pt, Pd, Rh, Ir, Ru, and Os at a metal loading of less than 0.8 g / L in the second proximal catalytic layer (21), and comprises one or more catalytically active metals selected from the group consisting of platinum group metals (PGM) including Pt, Pd, Rh, Ir, Ru, and Os at a metal loading of 0.1-2.0 g / L in the second distal catalytic layer (22), provided that the metal loading in the second distal catalytic layer (22) is higher than the metal loading in the second proximal catalytic layer (21), wherein the second distal catalytic layer (22) further comprises a catalyst sufficient to promote NO X The amount of tungsten (W) and / or molybdenum (Mo) converted into nitrogen dioxide.
8. The catalyst article (1) according to claim 7, wherein the platinum group metal selected for the second proximal catalytic layer (21) and the second distal catalytic layer (22) is platinum and / or palladium.
9. The catalyst product (1) according to claim 8, wherein the Pt:Pd ratio in the second distal catalytic layer (22) is 1:0 to 30:1, so the Pt:Pd ratio in the second proximal catalytic layer (21) is 1:9 to 9:
1.
10. The catalyst product (1) according to any one of claims 7 to 9, wherein the tungsten (W) in the second remote catalytic layer (22) is present in the form of tungsten oxide (WO3) in the range of 1 to 30 g / L.
11. The catalyst product (1) according to any one of claims 3 to 10, wherein the PGM loading in the catalytic layer (11, 12, 21, 22) is in the order: In-T≥Out-T>In-B>Out-B, but preferably In-T>Out-T>In-B>Out-B.
12. The catalyst article (1) according to any one of claims 3 to 11, wherein the first (11) and second (21) proximal catalytic layers are also formed in a manner sufficient to promote NO X The amount of adsorption-desorption and formation of NO2 by desorption at less than 200°C comprises cerium (Ce) oxide or cerium mixed oxide selected from ZrCe, MnCe, TiCe, PrCe oxide or a combination thereof.
13. The catalyst article (1) according to claim 12, wherein the cerium in the form of cerium oxide or cerium mixed oxide is present in an amount of 0.05 g / L to 0.5 g / L based on the total weight of cerium oxide or cerium mixed oxide.
14. The catalyst article (1) according to any one of claims 3 to 13, wherein the first (11) and second (21) proximal catalytic layers further comprise lanthanum (La), yttrium (Y), hafnium (Hf) or a combination thereof, but preferably lanthanum, calculated as stable oxide, in an amount ranging from 1 to 10 g / L, preferably 3 to 6 g / L, for promoting NOx of the first and second proximal catalytic layers. X and SO X Adsorption capacity.
15. The catalyst article (1) according to any one of claims 3 to 14, wherein the first (11) and second (21) proximal catalytic layers further comprise one or more zeolites with a high Si / Al2 ratio (SAR) selected from β, ZSM-5, chabazite (CHA), AEI, ferrierite (Fer), Y or a combination thereof, in an amount of 5-1000 g / L, but preferably 10-50 g / L, for increasing hydrocarbons and / or NO X Adsorption capacity.
16. The catalyst product (1) according to any one of claims 3 to 15, wherein the catalytic layer (11, 12, 21, 22) further comprises, in addition to the catalyst promoter, a catalyst selected from the group consisting of aluminum oxide, aluminum oxide (Al2O3), silicon oxide (SiO X ), silicon dioxide (SiO2), titanium oxide (TiO X ), titanium dioxide (TiO2) or a porous metal oxide porous support thereof.
17. The catalyst product (1) according to claim 16, wherein in all layers of the catalyst product (1), the coating amount in each coating layer is 10 to 200 g / L, preferably 40 to 100 g / L, more preferably 50 to 80 g / L, and wherein the porous metal oxide forms the remainder of the coating composition.
Citation Information
Patent Citations
Catalysts
EP0056729A2
Silica catalyst support for reduced sulphate emissions from diesel-fuelled engines
EP0377290A1
catalysis
GB1330842A
Purification of exhaust gas
US3947545A
Oxidation catalyst resistant to sulfation
US5145825A